Optical multilayers

A reddening-resistant layer in optical laminates addresses the issue of reddening under high temperatures by blocking heat transfer, maintaining color stability and transmittance.

JP7612163B2Active Publication Date: 2025-01-14SHANJIN OPTOELECTRONICS (SUZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021556564
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-01-31
Publication Date
2025-01-14
Estimated Expiration
2040-01-31

AI Technical Summary

Technical Problem

Optical laminates, particularly polarizing layers, experience reddening under harsh conditions such as high temperatures, leading to decreased durability and performance.

Method used

Incorporation of a reddening-resistant layer, such as a void-containing layer, adjacent to the optical functional layer to prevent, alleviate, or delay reddening by blocking heat transfer.

Benefits of technology

The reddening-resistant layer effectively maintains the optical properties of the laminate by minimizing changes in color coordinates and transmittance under extreme temperatures, ensuring durability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612163000006
    Figure 0007612163000006
  • Figure 0007612163000007
    Figure 0007612163000007
  • Figure 0007612163000008
    Figure 0007612163000008
Patent Text Reader

Abstract

The present application relates to an optical laminate or a reddening-resistant layer. The present application can provide an optical laminate or a reddening-resistant layer applied thereto that does not induce the so-called reddening phenomenon even when driven or maintained under very severe conditions (e.g., very high-temperature conditions).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority based on Korean Patent Application No. 10-2019-0037451 filed on March 29, 2019, the contents of which are incorporated herein by reference.

[0002] The present application relates to optical stacks or reddening resistant layers. [Background technology]

[0003] Increasingly, display devices are operated and / or maintained under more severe conditions, for example, display devices used in navigation and vehicle displays such as vehicle instrument panels are operated and / or maintained under very high temperatures in summer.

[0004] Depending on the application of the display device, the optical laminate such as a polarizing plate may be used in contact with a glass substrate called a cover glass. The cover glass or the like usually has superior thermal conductivity characteristics compared to the optical laminate. Therefore, heat is more efficiently transferred to the optical laminate in contact with the cover glass.

[0005] This requires that optical laminates such as polarizing plates maintain their durability under conditions that are particularly severe compared to conventional conditions (particularly conditions in which temperatures are maintained significantly higher than conventional conditions). Summary of the Invention [Problem to be solved by the invention]

[0006] The present application provides a reddening resistant layer, an optical stack and a display device. [Means for solving the problem]

[0007] Among the physical properties referred to in this specification, those whose results are influenced by the measurement temperature and / or the measurement pressure are the results measured at room temperature and / or normal pressure, unless otherwise specified.

[0008] The term "room temperature" refers to a natural temperature that is neither heated nor cooled, and means, for example, any one temperature within the range of 10° C. to 30° C., such as a temperature of about 23° C. or about 25° C. In this specification, the unit of temperature is ° C., unless otherwise specified.

[0009] The term "normal pressure" refers to the natural pressure without pressure increase or decrease, and usually means about 1 atmosphere of atmospheric pressure.

[0010] In the present specification, unless otherwise specified, the physical properties whose results are affected by the measurement humidity are physical properties measured at the natural humidity without any additional adjustment at room temperature and pressure.

[0011] The present application relates to an optical laminate, a display device, or a reddening-resistant layer. The optical laminate or the display device may include the reddening-resistant layer. In the present application, the term "reddening-resistant layer" may refer to any type of layer that can be applied to various optical laminates including an optical functional layer to prevent, mitigate, reduce, suppress, and / or delay the reddening of the optical laminate or the optical functional layer applied to the optical laminate. In particular, the reddening-resistant layer can effectively prevent, mitigate, reduce, suppress, and / or delay the reddening of the optical functional layer even when the optical functional layer, which is very sensitive to heat, such as the polarizing layer described below (particularly the iodine-based polarizing layer), is used and maintained under very harsh conditions such as a significantly high temperature.

[0012] The reddening refers to a phenomenon in which the optical laminate or the optical functional layer turns red. The occurrence or nonoccurrence of the reddening can be determined, for example, by the so-called CIE L * a * b * Color space a * The value can be checked through CIE L * a * b * In color space, * A positive value indicates that the object is more red.* The more negative the absolute value, the more green the object is. * The change in value is initial a * The positive increase in the value of the positive polarity indicates that the optically functional layer or the optical laminate has turned red.

[0013] In the present application, the term "reddening-resistant layer" refers to a layer applied to an optical laminate or together with an optical functional layer to prevent reddening of the optical laminate and / or the optical functional layer. * It may refer to any type of layer that can prevent, mitigate, reduce, inhibit and / or slow a change or increase in a value in a positive direction.

[0014] The reddening occurs easily mainly when heat is applied to the optical stack and / or the optical functional layer, and therefore the higher the temperature at which the optical stack and / or the optical functional layer are maintained, the more easily the reddening occurs.

[0015] In the present application, the term "reddening-resistant layer" refers to the above-mentioned a of the optical laminate or the optical functional layer after the heat resistance test. * The term "layer" refers to a layer that can reduce the absolute value of the change in the value to 2 or less. The heat resistance test refers to a test in which the optical laminate and / or the optical functional layer is maintained at about 95° C. for about 750 hours or at about 105° C. for about 250 hours. * The change in value is the a * Value a * a from a before the heat resistance test * Value (initial a * value)a * i The number a minus * a -a * i Or, conversely, initial a * Value (a * i ) to a after the heat resistance test * Value a * a The number a minus* i -a * a In light of the purpose of the reddening-resistant layer, * The change in value is the a * Value a * a From the initial a * Value a * i The number a minus * a -a * i It could be.

[0016] The heat resistance test may be a heat resistance test performed under harsher conditions than a normal heat resistance test. For example, the heat resistance test may be a heat resistance test performed in a state where the upper and lower surfaces (e.g., the entire upper surface and the entire lower surface) of the optical laminate and / or the optical functional layer are in contact with a glass substrate. Since the glass substrate is usually a material that transfers heat better than the optical laminate or the optical functional layer, if the heat resistance test is performed in a state where the glass substrate is in contact with the optical laminate or the optical functional layer, the effect of the applied heat on the optical laminate and / or the optical functional layer becomes greater. The type of glass substrate applied to the heat resistance test is not particularly limited, but in this specification, a soda lime glass substrate having a thickness of about 1.1 mm is used as a reference. A glass substrate is usually known to have a thermal conductivity of about 0.6 W / mK to 1.38 W / mK, and the optical laminate or the optical functional layer of the present application may prevent, mitigate, reduce, suppress, and / or delay reddening even if the heat resistance test is performed in a state where the glass substrate having the high thermal conductivity as described above is in contact with the optical laminate or the optical functional layer of the present application. The color coordinates and / or transmittance values ​​related to the heat resistance test mentioned in this specification are based on the application of soda lime glass having a thickness of about 1.1 mm, and in the heat resistance test, contact may mean a state in which the optical functional layer or an optical laminate including the same is in direct contact with the glass substrate (a soda lime glass plate having a thickness of about 1.1 mm).

[0017] The optical laminate of the present application can include an optical functional layer and the reddening-resistant layer formed on at least one surface of the optical functional layer. By including the reddening-resistant layer in the optical laminate, reddening of the optical laminate or the optical functional layer can be prevented, mitigated, reduced, suppressed, and / or delayed.

[0018] For example, the optical laminate or the optical functional layer contained therein has a CIE L * a * b * Color coordinates of a * Amount of change in value △a * The absolute value of may be within 2. The color coordinates referred to in this application are the results measured using a JASCO V-7100 Spectrophotometer.

[0019] [Formula 1] △a * =a * a -a * i

[0020] In formula 1, △a * is the color coordinate a * is the change in * a is the color coordinate a after the heat resistance test * value, a * i is the color coordinate a before the heat resistance test * Value (initial a * value).

[0021] The change amount △a * In other examples, the absolute value of may be within about 1.9, within about 1.8, within about 1.7, within about 1.6, within about 1.5, within about 1.4, within about 1.3, within about 1.2, within about 1.1, within about 1.0, within about 0.9, within about 0.8, within about 0.7, within about 0.6, within about 0.5, within about 0.4, within about 0.3, within about 0.2, or within about 0.1. *The absolute value of Δa means that the lower the value, the less reddening has occurred, so there is no lower limit. * The absolute value of may be 0 or more. * The absolute value of a * It may be the amount of change when the value changes in the positive direction compared to the initial value.

[0022] As described above, the heat resistance test is a process of maintaining the optical laminate and / or optical functional layer at about 95°C for about 750 hours or at about 105°C for about 250 hours. This heat resistance test can be performed with the upper and lower surfaces (entire upper and lower surfaces) of the optical laminate and / or optical functional layer in contact with the glass substrate (a soda lime glass plate with a thickness of about 1.1 mm). The contact can be direct contact. In such a * The amount of change in value can be measured by the method described in the Examples section of this specification.

[0023] When reddening occurs in the optical laminate and / or the optical functional layer, a phenomenon of a decrease in transmittance usually occurs. Since the optical laminate of the present application has excellent resistance to reddening, there is no change in transmittance or the change is minimized.

[0024] For example, the optical laminate or the optical functional layer may have an absolute value of change in transmittance ΔTs (single transmittance when the optical laminate is a polarizing plate or the optical functional layer is a polarizing layer) according to the following Equation 2 in the same heat resistance test as that used to confirm Equation 1, within 5. The transmittance is measured using a JASCO V-7100 spectrophotometer for light in the visible light region, for example, light in the range of about 380 nm to 780 nm.

[0025] [Formula 2] △Ts=T a -T i

[0026] In Equation 2, ΔTs is the change in the transmittance (when the optical laminate is a polarizing plate or the optical functional layer is a polarizing layer, the single transmittance), and T a is the transmittance after the heat resistance test (when the optical laminate is a polarizing plate or the optical functional layer is a polarizing layer, it is the single transmittance) (transmittance after the heat resistance durability test), and T i is the transmittance before the heat resistance test (when the optical laminate is a polarizing plate or the optical functional layer is a polarizing layer, it is the single transmittance).

[0027] In other examples, the absolute value of the change amount ΔTs is about 4.9 or less, about 4.8 or less, about 4.7 or less, about 4.6 or less, about 4.5 or less, about 4.4 or less, about 4.3 or less, about 4.2 or less, about 4.1 or less, about 4 or less, about 3.9 or less, about 3.8 or less, about 3.7 or less, about 3.6 or less, about 3.5 or less, about 3.4 or less, about 3.3 or less, about 3.2 or less, about 3.1 or less, about 3 or less, about 2.9 or less, about 2.8 or less, about 2.7 or less, about It may be 2.6 or less, about 2.5 or less, about 2.4 or less, about 2.3 or less, about 2.2 or less, about 2.1 or less, about 1.9 or less, about 1.8 or less, about 1.7 or less, about 1.6 or less, about 1.5 or less, about 1.4 or less, about 1.3 or less, about 1.2 or less, about 1.1 or less, about 1.0 or less, about 0.9 or less, about 0.8 or less, about 0.7 or less, about 0.6 or less, about 0.5 or less, about 0.4 or less, about 0.3 or less, about 0.2 or less, or about 0.1 or less. The lower limit of the absolute value of the change amount ΔTs is 0, since the less the change in the transmittance, the less the reddening. In other examples, the absolute value of such a change amount ΔTs may be substantially greater than 0.

[0028] The heat resistance test for measuring the amount of change in the transmittance is * The test can be carried out under the same conditions as the heat resistance test for measuring the amount of change in value. The transmittance can be measured by the method described in the examples of this specification.

[0029] The optical laminate includes an optically functional layer. The term "optically functional layer" refers to a layer that exhibits at least one optically intended function. Examples of the optically intended functions include generation of polarized light such as linear polarization or circular polarization, reflection, refraction, absorption, scattering, and / or phase retardation. In the optical field, various layers having such functions are known, and examples of the optically functional layer applied in the present application may include all types of layers in which reddening is a problem among the known optically functional layers.

[0030] In one example, the optical functional layer may be a polarizing layer or a retardation layer. In this specification, the case where the optical functional layer is a polarizing layer is described, but the type of the optical functional layer is not limited to a polarizing layer. In addition, when the optical functional layer is a polarizing layer, the optical laminate may be a polarizing plate.

[0031] In this specification, the terms "polarizing layer" and "polarizing plate" refer to different objects. The term "polarizing layer" refers to, for example, a multilayer or single layer that exhibits a polarizing function, and the term "polarizing plate" may refer to a laminate that includes the polarizing layer and other elements that do not have a polarizing function. Examples of other elements that are included together with the polarizing layer include, but are not limited to, a protective film or protective layer for the polarizing layer, the reddening-resistant layer, a retardation layer, an adhesive layer, a pressure-sensitive adhesive layer, a hard coat layer, or a low reflection layer.

[0032] The type of polarizing layer to be applied in the present application is not limited in principle. The most common polarizing layer known in the art is a linear absorption type polarizing layer, which is a so-called polyvinyl alcohol (hereinafter, referred to as PVA) polarizing layer. In this specification, the term "PVA" means polyvinyl alcohol or its derivatives unless otherwise specified. As the PVA polarizing layer, for example, a stretched PVA film in which an absorption anisotropic substance such as iodine or a dichroic dye is adsorbed and oriented, or a so-called coating type PVA polarizing layer in which PVA is applied in a coating method to form a thin polarizing layer, etc. are known, and in the present application, all of the above types of polarizing layers can be applied. In addition to the PVA polarizing layer, a polarizing plate formed of a liquid crystal compound such as LLC (Lyotropic Liquid Crystal), a polarizing layer formed by aligning a polymerizable liquid crystal compound (so-called RM (Reactive Mesogen)) and a dichroic dye in a GH (Guest-Host) method, etc. can also be applied in the present application.

[0033] In the present application, particularly when an iodine-based polarizing layer is used as the polarizing layer, reddening of the iodine-based polarizing layer can be effectively prevented, mitigated, reduced, suppressed, and / or delayed.

[0034] The iodine-based polarizing layer is a polarizing layer in which an iodine-based substance is used as the absorption anisotropic substance. As the absorption anisotropic substance, typically, an iodine-based substance or a dichroic dye such as an azo dye may be used. In the former case, it may be called an iodine-based polarizing layer, and in the latter case, it may be called a dye-based polarizing layer. An iodine-based polarizing layer generally exhibits superior optical performance (e.g., high transmittance, high polarization degree, and high contrast) compared to a dye-based polarizing layer. However, the heat resistance of an iodine-based polarizing layer is significantly lower than that of a dye-based polarizing layer. In particular, the iodine-based substance contained in an iodine-based polarizing layer decomposes under high temperature and / or high humidity conditions to form I 2The dye-based polarizing layer may easily generate a substance that induces reddening through inappropriate absorption of the visible light region. Therefore, in applications where durability under high temperature and / or high humidity conditions is essential, a dye-based polarizing layer may be applied even if it loses optical properties. However, according to the present application, even when an iodine-based polarizing layer is applied, and even when such an iodine-based polarizing layer is maintained and used under harsh conditions such as a significantly high temperature condition, the reddening of the iodine-based polarizing layer can be effectively prevented, mitigated, reduced, suppressed, and / or delayed. Therefore, according to the present application, the disadvantages of the iodine-based polarizing layer can be solved while obtaining its advantages.

[0035] The iodine-based polarizing layer may be an iodine-based PVA polarizing layer, which is a polarizing layer in which an iodine-based material is oriented in the stretched PVA film or the coating type PVA polarizing layer.

[0036] According to the present application, even when an iodine-based polarizing layer having poor durability as described above is applied, it is possible to effectively prevent the reddening phenomenon while obtaining the advantages of the polarizing layer, but the type of polarizing layer applied in the present application is not limited to an iodine-based polarizing layer.

[0037] The polarizing layer used in the examples of the present application is an iodine-based PVA polarizing layer, which is usually manufactured by dyeing and stretching a PVA disk film. In the manufacturing process of the PVA polarizing layer, additional processes such as swelling, crosslinking, washing and / or color complementation processes may be optionally performed, and the manufacturing process of the PVA polarizing layer through such processes is well known.

[0038] In one example, in order to ensure the durability, particularly the high temperature reliability, of the optical laminate, an iodine-based PVA polarizing layer containing a zinc component may be used as the polarizing layer. Examples of the zinc component include zinc and / or zinc ions. The PVA polarizing layer may also contain a potassium component, such as potassium or potassium ions, as an additional component. Using a polarizing layer containing such a component can provide an optical laminate that stably maintains durability even under high temperature conditions.

[0039] The ratio of the potassium and / or zinc component may be further adjusted. For example, the ratio K / Zn of the potassium component K to the zinc component Zn contained in the PVA polarizing layer may be in the range of 0.2 to 8 in one example. In another example, the ratio K / Zn may be about 0.4 or more, 0.6 or more, 0.8 or more, 1 or more, 1.5 or more, 2 or more, or 2.5 or more, and may be 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, about 5 or less, about 4.5 or less, or about 4 or less. The ratio may be a molar ratio or a weight ratio.

[0040] The content of the potassium component contained in the PVA polarizing layer may be about 0.1 to 2 wt%. In other examples, the ratio of the potassium component may be about 0.15 wt% or more, about 0.2 wt% or more, about 0.25 wt% or more, about 0.3 wt% or more, about 0.35 wt% or more, 0.4 wt% or more, about 0.45 wt% or more, about 0.5 wt% or more, about 0.55 wt% or more, about 0.6 wt% or more, about 0.65 wt% or more, about 0.7 wt% or more, about 0.75 wt% or more, or about 0.8 wt% or more, and about 1.95 wt% or less, about 1.9 wt% or less, about 1.85 wt% or less, about 1.8 wt% or less, about 1.9 ...8 wt% or less, about 1.9 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less, about 1.8 wt% or less % or less by weight, about 1.75% or less by weight, about 1.7% or less by weight, about 1.65% or less by weight, about 1.6% or less by weight, about 1.55% or less by weight, about 1.5% or less by weight, about 1.45% or less by weight, about 1.4% or less by weight, about 1.35% or less by weight, about 1.3% or less by weight, about 1.25% or less by weight, about 1.2% or less by weight, about 1.15% or less by weight, about 1.1% or less by weight, about 1.05% or less by weight, about 1% or less by weight, about 0.95% or less by weight, about 0.9% or less by weight, or about 0.85% or less by weight.

[0041] In one example, the ratio of the potassium component and the zinc component may be contained so as to satisfy the following mathematical formula 3.

[0042] [Formula 3] 0.70~1=1 / (1+0.025d / R)

[0043] In Equation 3, d is the thickness (μm) of the PVA polarizing layer, and R is the ratio K / Zn of the weight ratio K (unit: weight%) of the potassium component contained in the polarizing layer to the weight ratio Zn (unit: weight%) of the zinc component.

[0044] By including potassium and zinc components in the polarizing layer, it is possible to provide a polarizing layer having excellent reliability at high temperatures.

[0045] In Formula 3, the value of 1 / (1+0.025d / R) may be, in other examples, about 0.75 or more, about 0.8 or more, or about 0.85 or more, and the value of 1 / (1+0.025d / R) may be about 0.97 or less, about 0.95 or less, or about 0.93 or less.

[0046] In the above description, the content of potassium and / or zinc components can be measured by the method described in the Examples of this specification.

[0047] The polarizing layer used in the examples of the present application may be a polarizing layer manufactured by a known method for manufacturing a polarizing layer. In addition, when a polarizing layer containing potassium and / or zinc is to be used as the polarizing layer in the present application, the process conditions may be controlled so that the polarizing layer contains zinc and / or potassium during the manufacturing process of the known polarizing layer.

[0048] As described above, the PVA polarizing layer is generally prepared by dyeing and stretching a PVA film (disc film), and optionally, swelling, crosslinking, washing and / or color-complementing processes may be additionally performed during the preparation of the PVA polarizing layer. The stretching process may be performed as a separate process or may be performed simultaneously with other processes such as the dyeing, swelling and / or crosslinking. In such a preparation process, a treatment solution such as a dye solution, a crosslinking solution, a swelling solution, a washing solution and / or a color-complementing solution is applied, and by adjusting the components of the treatment solution, it is possible to determine whether or not the potassium and / or zinc components are included, or to adjust the ratio thereof.

[0049] In the dyeing step, an absorbent anisotropic substance can be adsorbed and / or oriented in the PVA film. Such a dyeing step can be carried out together with the stretching step, if necessary. The dyeing can be carried out by immersing the film in a solution containing an absorbent anisotropic substance, for example, an iodine solution. The iodine solution can be, for example, iodine I 2and an aqueous solution containing iodine ions by an iodide compound as a solubilizing agent. As the iodide compound, for example, potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, titanium iodide, etc. may be used. The concentration of iodine and / or iodide ions in the iodine solution may be adjusted in consideration of the optical properties of the intended polarizing layer, and such an adjustment method is known. Usually, the content of iodine in the dye solution (iodine solution) is about 0.01 to 5% by weight, and the concentration of the iodide compound may be about 0.01 to 10% by weight. In other examples, the iodine content may be 0.05% by weight or more, 0.1% by weight or more, or 0.15% by weight or more, and may be about 4.5% by weight or less, 4% by weight or less, 3.5% by weight or less, 3% by weight or less, 2.5% by weight or less, 2% by weight or less, 1.5% by weight or less, 1% by weight or less, or 0.5% by weight or less. In other examples, the concentration of the iodine compound may be 0.05% by weight or more, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, or 2% by weight or more, and may be about 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, or 3% by weight or less. In the dyeing process, the temperature of the iodine solution is usually about 20° C. to 50° C. or 25° C. to 40° C., and the immersion time is usually about 10 to 300 seconds or 20 to 240 seconds, but is not limited to these.

[0050] The stretching step is generally performed by uniaxial stretching, but other stretching methods such as biaxial stretching may be applied as necessary. Such stretching may be performed together with the dyeing and / or the crosslinking step described below. The stretching method is not particularly limited, and for example, a wet method may be applied. In such a wet method, for example, stretching is generally performed after dyeing. Stretching may be performed together with crosslinking, and may be performed multiple times or in multiple stages. The above-mentioned iodide compound may be contained in the treatment liquid applied to the wet stretching method. The concentration of the iodide compound in the treatment liquid may be about 0.01 to 10% by weight. In other examples, the concentration of the iodide compound may be 0.05% by weight or more, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, or 2% by weight or more, and may be about 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, or 3.5% by weight or less. In the stretching, the treatment temperature is usually 25°C or higher, about 30°C to 85°C or 40°C to 70°C, and the treatment time is usually 10 seconds to 800 seconds or 30 seconds to 500 seconds, but is not limited thereto. In the stretching process, the total stretching ratio can be adjusted in consideration of the orientation characteristics, etc., and based on the original length of the PVA film, the total stretching ratio may be about 3 times to 10 times, 4 times to 8 times, or 5 times to 7 times, but is not limited thereto. In the above-mentioned total stretching ratio, when stretching is also performed in other steps such as swelling, dyeing and / or crosslinking steps other than the stretching step, the total stretching ratio may mean a cumulative stretching ratio including the stretching in each step. Such a total stretching ratio can be adjusted within an appropriate range in consideration of the orientation, the processability of the polarizing layer, the possibility of stretching breakage, etc.

[0051] In the manufacturing process of the polarizing layer, a swelling process can be carried out in addition to the dyeing and stretching, which is usually carried out before the dyeing process. The swelling can clean the contaminants and anti-blocking agent on the PVA film surface, and also has the effect of reducing unevenness such as uneven dyeing.

[0052] In the swelling step, water, distilled water, pure water, or the like may usually be used. The main component of the treatment liquid is water, and if necessary, a small amount of additives such as iodide compounds such as potassium iodide or surfactants, alcohol, or the like may be contained. The treatment temperature in the swelling step is usually about 20°C to 45°C or 20°C to 40°C, but is not limited thereto. Since uneven swelling can induce uneven dyeing, the process variables can be adjusted so that the occurrence of such uneven swelling is suppressed as much as possible. In the swelling step, any appropriate stretching can also be performed. The stretching ratio can be about 6.5 times or less, 1.2 to 6.5 times, 2 times to 4 times, or 2 times to 3 times based on the original length of the PVA film. The stretching in the swelling step can be controlled to be small in the stretching step performed after the swelling step, so that stretching breakage of the film does not occur.

[0053] The crosslinking step can be carried out using a crosslinking agent such as a boron compound. The order of the crosslinking step is not particularly limited, and for example, the crosslinking step can be carried out together with the dyeing and / or stretching step, or can be carried out separately. The crosslinking step can also be carried out multiple times. As the boron compound, boric acid or borax can be used. The boron compound can generally be used in the form of an aqueous solution or a mixed solution of water and an organic solvent, and an aqueous boric acid solution is usually used. The concentration of boric acid in the aqueous boric acid solution can be selected within an appropriate range in consideration of the degree of crosslinking and the heat resistance resulting therefrom. The aqueous boric acid solution can also contain an iodide compound such as potassium iodide. The concentration of the iodide compound in the aqueous boric acid solution can be about 0.01 to 10% by weight. In other examples, the concentration of the iodide compound may be 0.05% by weight or more, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, or 2% by weight or more, and may be about 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, or 3.5% by weight or less. The crosslinking step can be performed by immersing the PVA film in an aqueous boric acid solution or the like, and the treatment temperature in this process is usually in the range of 25°C or more, 30°C to 85°C or about 30°C to 60°C, and the treatment time is usually about 5 seconds to 800 seconds, or about 8 seconds to 500 seconds.

[0054] In the manufacturing process of the polarizing layer, a metal ion treatment may be performed, which is usually called a complementary color process. For example, this treatment is performed by immersing the PVA film in an aqueous solution containing a metal salt. Through this, a metal component such as a metal ion can be contained in the polarizing layer, and the type and ratio of the metal component can be adjusted in this process. Examples of metal ions that can be applied include ions of transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, or iron, and the color tone can be adjusted by selecting an appropriate type from among them.

[0055] In order to manufacture a polarizing layer containing zinc, a zinc component may be contained in the treatment liquid (aqueous solution containing a metal salt) applied in the complementary color process. However, the zinc component may be applied in other processes as necessary, and in such cases, the zinc component may be contained in other treatment liquids such as a dyeing liquid or a crosslinking liquid, or in a separate treatment liquid. The zinc component may be introduced by dissolving one or more zinc salts selected from zinc chloride, zinc iodide, zinc sulfate, zinc nitrate, and zinc acetate in the aqueous solution. In such a case, in order to achieve a target zinc content, the concentration of the zinc salt may be adjusted to about 0.01 to 10% by weight. In other examples, the concentration of the zinc salt may be 0.05% by weight or more, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, or 2% by weight or more, or about 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, or 3% by weight or less. If necessary, a potassium component may also be contained in the treatment liquid. Examples of the potassium component include potassium salts such as potassium iodide. The concentration of the potassium salt may be about 0.01 to 10% by weight. In other examples, the concentration may be 0.05% by weight or more, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 2% by weight or more, 2.5% by weight or more, 3% by weight or more, 3.5% by weight or more, 4% by weight or more, 4.5% by weight or more, or 5% by weight or more, or 9% by weight or less, 8% by weight or less, 7% by weight or less, or 6% by weight or less. By applying zinc salt or potassium salt in the complementary color process as described above, the desired level of zinc and potassium components can be contained in the polarizing layer.

[0056] In the manufacturing process of the polarizing layer, a washing process may be performed after dyeing, crosslinking, and stretching. This washing process may be performed usually before the color complementation process, and may be performed using water. If necessary, the water used in the washing process may contain an appropriate amount of other components such as iodine, iodide, and other metal salts, or liquid alcohols such as methanol, ethanol, isopropyl alcohol, butanol, or propanol.

[0057] After the above steps, a drying step may be performed to manufacture the polarizing layer. The drying step may be performed at an appropriate temperature for an appropriate time in consideration of, for example, the moisture content required for the polarizing layer, and the like, and the conditions are not particularly limited.

[0058] As described above, the zinc and / or potassium component may be included in the polarizing layer in the above process. However, the method for manufacturing the polarizing layer containing the zinc and / or potassium component is not limited to the above. For example, the zinc component may be included in the polarizing layer in a process other than the complementary color process by including a zinc salt in a treatment solution applied to the swelling, dyeing, crosslinking, stretching and / or washing process. In addition, since a potassium component such as potassium iodide may be included in the treatment solution applied to the swelling, dyeing, crosslinking, stretching and / or washing process, the ratio of the potassium component may be adjusted in this process. Those skilled in the art can appropriately adopt a general method for manufacturing a polarizing layer to include a desired level of zinc and / or potassium component in the polarizing layer according to the purpose.

[0059] The thickness of the polarizing layer is not limited. In the present application, a generally known polarizing layer may be applied, and therefore the thickness of the polarizing layer is generally the same. The thickness of the polarizing layer may be in the range of 5 μm to 80 μm, but is not limited thereto.

[0060] The optical laminate of the present application includes the reddening-resistant layer.

[0061] The present application relates to an optical stack or a display device comprising said reddening-resistant layer or to said reddening-resistant layer.

[0062] The term "reddening-resistant layer" refers to a layer capable of preventing, mitigating, reducing, suppressing and / or delaying reddening of the optical laminate and / or optical functional layer, as mentioned above. Reddening of the optical laminate and / or optical functional layer is expected to occur due to heat and / or moisture, or at least accelerated by heat and / or moisture. With the expansion of the use of display devices, the optical laminate and / or optical functional layer are more frequently exposed to higher temperatures, and this frequently causes the optical functional layer or optical laminate, which did not previously cause reddening problems, to cause reddening in the new use.

[0063] As a result, the reddening-resistant layer can be a layer that serves to block heat applied to the optical laminate and / or optical functional layer, reduce the level of heat applied, or slow down the rate of heat transfer.

[0064] In one example, the reddening-resistant layer may be a void-containing layer (porous layer) described below, or a laminate including the void-containing layer (porous layer), and may be a layer that is sufficiently adjacent to the optical functional layer. By making the reddening-resistant layer a void-containing layer (porous layer) or a layer that includes the void-containing layer (porous layer), it is possible to effectively block heat transfer. The optical functional layer may be a layer that causes reddening, such as the iodine-based polarizing layer described above. In addition, the reddening-resistant layer being sufficiently adjacent to the optical functional layer means that the position of the reddening-resistant layer and the distance between the reddening-resistant layer and the optical functional layer are adjusted so that the reddening-resistant layer can block heat transfer to the optical functional layer at a level that can prevent, mitigate, reduce, suppress and / or delay reddening. For example, even if there is a layer having a similar structure to the reddening-resistant layer of the present application described below, unless such a layer is located in a position and at a distance that can block the transmission of heat to the optical functional layer, such a layer cannot be called a reddening-resistant layer as defined in the present application. For example, being sufficiently adjacent to each other may mean that the distance between the optically functional layer that causes reddening and the reddening-resistant layer is within about 90 μm, within about 85 μm, within about 80 μm, within about 75 μm, within about 70 μm, within about 65 μm, within about 60 μm, within about 55 μm, within about 50 μm, within about 45 μm, within about 40 μm, within about 35 μm, within about 30 μm, within about 25 μm, within about 20 μm, within about 15 μm, within about 10 μm, within about 5 μm, within about 1 μm, within about 0.9 μm, within about 0.8 μm, within about 0.7 μm, within about 0.6 μm, within about 0.5 μm, within about 0.4 μm, within about 0.3 μm, or within about 0.2 μm. The sufficient proximity also includes the case where the optical functional layer and the reddening-resistant layer are in contact with each other, and in such a case, the distance is 0 μm. Therefore, the lower limit of the distance is 0 μm. In other examples, the distance may be about 0.01 μm or more, about 0.02 μm or more, about 0.03 μm or more, about 0.04 μm or more, about 0.05 μm or more, about 0.09 μm or more, or about 0.1 μm or more. The distance may be the shortest distance, the maximum distance, or the average distance between the opposing surfaces of the reddening-resistant layer and the optical functional layer.

[0065] In one example, the reddening-resistant layer can be a void-containing layer (porous layer) described later, or a laminate containing the void-containing layer (porous layer), and can be a layer having a sufficient thickness to prevent reddening of the optical functional layer. That is, even if the reddening-resistant layer is a void-containing layer (porous layer) or a layer containing the void-containing layer (porous layer), if the appropriate thickness is not ensured, the transfer of heat cannot be effectively blocked. For example, even if a layer having a similar structure to the reddening-resistant layer of the present application described later exists, if such a layer does not have a thickness sufficient to block the transfer of heat to the optical functional layer, such a layer cannot be called a reddening-resistant layer as referred to in the present application. In one example, the sufficient thickness may be, for example, about 200 nm or more, about 250 nm or more, about 300 nm or more, about 350 nm or more, about 400 nm or more, about 450 nm or more, about 500 nm or more, about 550 nm or more, about 600 nm or more, about 650 nm or more, about 700 nm or more, about 750 nm or more, about 800 nm or more, about 850 nm or more, or about 900 nm or more. The upper limit of the thickness is not particularly limited. The thicker the reddening-resistant layer, the better the effect of preventing, mitigating, reducing, suppressing and / or delaying heat. Therefore, the upper limit of the thickness of the reddening-resistant layer or the void-containing layer (porous layer) can be selected in consideration of the thickness required for the optical laminate, as long as the effect of preventing, mitigating, reducing, suppressing and / or delaying heat is ensured, and there is no particular limit. In one example, the thickness of the reddening-resistant layer or void-containing layer (porous layer) may be about 3,000 nm or less, about 2,900 nm or less, about 2,800 nm or less, about 2,700 nm or less, about 2,600 nm or less, about 2,500 nm or less, about 2,400 nm or less, about 2,300 nm or less, about 2,200 nm or less, about 2,100 nm or less, about 2,000 nm or less, or about 1,950 nm or less.

[0066] In one embodiment, the reddening-resistant layer has a thermal diffusion property within a predetermined range. Rate For example, the reddening-resistant layer may be a layer having a thermal diffusion coefficient measured at 95° C. by forming the reddening-resistant layer on a polymer film to produce a laminate. Rate The thermal diffusion of the polymer film alone RateThermal diffusion is 90% or less compared to Rate may have:

[0067] In such a case, the reddening-resistant layer can satisfy the following formula 4.

[0068] In the present application, the term "reddening-resistant layer" may refer to the void-containing layer (porous layer) itself or a laminate including at least the void-containing layer (porous layer). Therefore, the reddening-resistant layer in the following formula 4 may be the void-containing layer (porous layer) or a laminate including it.

[0069] [Formula 4] H L ≦0.9×H P

[0070] In formula 4, H L The thermal diffusion of the laminate of the polymer film and the reddening-resistant layer formed on one side of the polymer film Rate and H P is the thermal diffusion of the polymer film Rate It is.

[0071] In the present specification, the thermal diffusion Rate The type of polymer film for measuring is not particularly limited. For example, the polymer film in Equation 4 may be a TAC (Triacetyl cellulose) film having a thickness of about 60 μm. Rate (95° C.) is, in another example, the thermal diffusion of the TAC film. Rate (95℃)H PAbout 89% or less, about 88% or less, about 87% or less, about 86% or less, about 85% or less, about 84% or less, about 83% or less, about 82% or less, about 81% or less, about 80% or less, about 79% or less, about 78% or less, about 77% or less, about 76% or less, about 75% or less, about 74% or less, about 73% or less, about 72% or less, about 71% or less, about 7 about 0% or less, about 69% or less, about 68% or less, about 67% or less, about 66% or less, or about 65% or less, or about 10% or more, about 11% or more, about 12% or more, about 13% or more, about 14% or more, about 15% or more, about 16% or more, about 17% or more, about 18% or more, about 19% or more, about 20% or more, about 21% or more, about 22% or more, about About 23% or more, about 24% or more, about 25% or more, about 26% or more, about 27% or more, about 28% or more, about 29% or more, about 30% or more, about 31% or more, about 32% or more about 33% or more, about 34% or more, about 35% or more, about 36% or more, about 37% or more, about 38% or more, about 39% or more, about 40% or more, about 41% or more, about 42% or more or above, about 43% or more, about 44% or more, about 45% or more, about 46% or more, about 47% or more, about 48% or more, about 49% or more, about 50% or more, about 51% or more, about 52% or more, about 53% or more, about 54% or more, about 55% or more, about 56% or more, about 57% or more, about 58% or more, about 59% or more, or about 60% or more.

[0072] Therefore, in Equation 4, the H P The coefficient by which H is multiplied may be 0.89, 0.88, 0.87, 0.86, 0.85, 0.84, 0.83, 0.82, 0.81, 0.80, 0.79, 0.78, 0.77, 0.76, 0.75, 0.74, 0.73, 0.72, 0.71, 0.70, 0.69, 0.68, 0.67, 0.66, or 0.65. L is approximately 0.10 x H P Above, approx. 0.11 x H P Above, approx. 0.12 x H PAbove, approx. 0.13 x H P Above, approx. 0.14 x H P Above, approx. 0.15 x H P Above, approx. 0.16 x H P Above, approx. 0.17 x H P Above, approx. 0.18 x H P Above, approx. 0.19 x H P Above, approx. 0.20 x H P Above, approx. 0.21 x H P Above, approx. 0.22 x H P Above, approx. 0.23 x H P Above, approx. 0.24 x H P Above, approx. 0.25 x H P Above, approx. 0.26 x H P Above, approx. 0.27 x H P Above, approx. 0.28 x H P Above, approx. 0.29 x H P Above, approx. 0.30 x H P Above, approx. 0.31 x H P Above, approx. 0.32 x H P Above, approx. 0.33 x H P Above, approx. 0.34 x H P Above, approx. 0.35 x H P Above, approx. 0.36 x H P Above, approx. 0.37 x H P Above, approx. 0.38 x H P Above, approx. 0.39 x H P Above, approx. 0.40 x H P Above, approx. 0.41 x H P Above, approx. 0.42 x H P Above, approx. 0.43 x H P Above, approx. 0.44 x H P Above, approx. 0.45 x H P Above, approx. 0.46 x H P Above, approx. 0.47 x H P Above, approx. 0.48 x H P Above, approx. 0.49 x H P Above, approx. 0.50 x H P Above, approx. 0.51 x H P Above, approx. 0.52 x H P Above, approx. 0.53 x H P Above, approx. 0.54 x H P Above, approx. 0.55 x H P Above, approx. 0.56 x HP Above, approx. 0.57 x H P Above, approx. 0.58 x H P Above, approx. 0.59 x H P or more than 0.60 x H P It may be more than that.

[0073] The surface properties of the reddening-resistant layer or void-containing layer (porous layer) can be controlled. The reddening-resistant layer or void-containing layer (porous layer) can be directly attached to the optical functional layer or attached to another layer of the optical laminate adjacent to the optical functional layer in order to be adjacent to the optical functional layer in which reddening must be prevented, mitigated, reduced, suppressed and / or delayed. In such a case, by controlling the surface properties of the reddening-resistant layer or void-containing layer (porous layer), the reddening-resistant layer or void-containing layer (porous layer) can be attached to the optical functional layer or another layer with excellent adhesion, thereby more effectively preventing, mitigating, reducing, suppressing and / or delaying the reddening. For example, the reddening-resistant layer or void-containing layer (porous layer) can include at least one surface having a surface area ratio of about 0.02 or more as measured by an atomic force microscope (AFM). For example, at least one of the main surfaces of the reddening-resistant layer or the void-containing layer (porous layer), or both of the surfaces, may have the above surface area ratio. In one example, the surface of the reddening-resistant layer or the void-containing layer (porous layer) having at least the above surface area ratio may be the surface facing the optically functional layer or other layer to which the reddening-resistant layer or the void-containing layer (porous layer) is attached. In other examples, the surface area ratio of the reddening-resistant layer or the void-containing layer (porous layer) may be about 0.022 or more, about 0.024 or more, about 0.026 or more, about 0.028 or more, about 0.03 or more, about 0.032 or more, or about 0.034 or more, or about 0.5 or less, about 0.45 or less, about 0.4 or less, about 0.35 or less, about 0.3 or less, or about 0.25 or less. The surface area ratio can be measured by the method described in the examples.

[0074] The reddening-resistant layer or void-containing layer (porous layer) may exhibit a desired level of reflectance against infrared rays. Since heat is also transferred in the form of infrared rays, the desired anti-reddening properties can be ensured when the layer exhibits an appropriate reflectance against the infrared rays. In this specification, the term "infrared rays" may mean electromagnetic waves having any one wavelength within the range of about 800 nm to 1,300 nm, or a wavelength within a partial range within the range, or the entire range. Therefore, the infrared reflectance may be a reflectance for any one wavelength within the range of 800 nm to 1,300 nm, or an average reflectance for a partial range or the entire range within the range. The reflectance may be measured according to the method described in the examples of this specification. The reddening-resistant layer or void-containing layer (porous layer) may have an infrared reflectance of about 2% or more. In other examples, the reflectance may be about 2.5% or more, about 3% or more, about 3.5% or more, or about 4% or more. The reflectance is not particularly limited in upper limit because the higher the reflectance value, the more the anti-reddening layer or the void-containing layer (porous layer) can properly block and / or delay the heat applied to the optical laminate and / or the optical functional layer. Exemplarily, the infrared reflectance may be about 10% or less, about 9% or less, about 8% or less, about 7% or less, about 6% or less, or about 5% or less.

[0075] As the reddening-resistant layer or the void-containing layer (porous layer), various layers can be applied without special restrictions as long as they have a suitable transmittance applicable to the optical laminate and the above-mentioned characteristics (thermal diffusivity, surface area ratio and / or reflectance). Since the above-mentioned characteristics can prevent, mitigate, reduce, suppress and / or delay reddening, all layers that can properly ensure the transmittance can be theoretically applied in the present application. The transmittance required in the optical laminate may be about 70% or more, about 75% or more, about 80% or more, about 85% or more, or about 90% or more. The higher the transmittance, the more suitable it is, and the upper limit is not particularly limited. For example, the transmittance may be about 100% or less, about 95% or less, or about 90% or less. The transmittance may be the transmittance for light in the visible light region, for example, any one wavelength within the range of about 380 nm to 780 nm, or a certain region of the wavelength within the range, or the entire region, or the average transmittance. When a void-containing layer (porous layer) is applied as a reddening-resistant layer or a laminate including the void-containing layer (porous layer) is applied, the voids present in the reddening-resistant layer can effectively block heat transfer, but the voids can scatter or diffract light in the optical laminate, which can be disadvantageous in terms of transmittance. However, in this application, as described later, by controlling the form of the voids, there is no decrease in transmittance due to the scattering or diffraction of light, or at least such decrease can be limited to a level that does not cause problems in use.

[0076] As the reddening-resistant layer, for example, a void-containing layer (porous layer) or a layer including a void-containing layer (porous layer) can be applied. That is, as described above, in this application, the reddening-resistant layer can refer to the void-containing layer (porous layer) itself, or it can refer to a laminate including the void-containing layer (porous layer) and other layers, so long as the purpose of preventing reddening is satisfied. In one example, the reddening-resistant layer includes the void-containing layer (porous layer) to achieve the above-mentioned characteristics (thermal diffusion). Rate , surface area ratio and / or infrared reflectance). RateThe surface area ratio and / or infrared reflectance may be for the void-containing layer (porous layer) or for a laminate including at least the void-containing layer (porous layer). The types of other elements included in the reddish layer together with the void-containing layer (porous layer) are not particularly limited, and may be, for example, elements constituting an optical laminate such as the polarizing layer or its protective film, a retardation film, etc.

[0077] The void-containing layer is a layer containing at least one void therein, and the reddening-resistant layer can prevent, mitigate, reduce, inhibit and / or delay the transfer of heat through the void. In the present application, when the void-containing layer is referred to as a porous layer, the void-containing layer contains at least two voids therein. The above-mentioned physical properties, such as thermal diffusion, Rate In order to ensure the surface area ratio and / or reflectance, it is important that the reddening-resistant layer includes the void-containing layer (porous layer). In this case, the shape of the voids included in the void-containing layer (porous layer) is not particularly limited, and for example, voids having a substantially spherical or ellipsoidal shape or various other shapes may all be applied.

[0078] The size (diameter) of the void may be within the range of approximately 0.5 nm to 100 nm. When the void is spherical, the size of the void means the particle diameter thereof, and when the void is not spherical, the size of the void means the particle diameter of the void when the void is assumed to be a sphere of the same volume. In other examples, the size of the void may be about 1 nm or more, about 2 nm or more, about 3 nm or more, about 4 nm or more, about 5 nm or more, about 6 nm or more, about 7 nm or more, about 8 nm or more, about 9 nm or more, about 10 nm or more, about 11 nm or more, about 12 nm or more, about 13 nm or more, about 14 nm or more, about 15 nm or more, about 16 nm or more, about 17 nm or more, about 18 nm or more, about 19 nm or more, about 20 nm or more, about 21 nm or more, about 22 nm or more. or greater than about 23 nm, greater than about 24 nm, greater than about 25 nm, greater than about 26 nm, greater than about 27 nm, greater than about 28 nm, greater than about 29 nm, greater than about 31 nm, greater than about 32 nm, greater than about 33 nm, greater than about 34 nm, greater than about 35 nm, greater than about 36 nm, greater than about 37 nm, or greater than about 38 nm; or less than about 99 nm, less than about 98 nm, less than about 97 nm, less than about 96 nm, less than about 95 nm, less than about 94 nm, less than about 93 nm, less than about 92nm or less, about 91nm or less, about 90nm or less, about 89nm or less, about 88nm or less, about 87nm or less, about 86nm or less, about 85nm or less, about 84nm or less, about 83nm or less, about 82nm or less, about 81nm Below, about 79 nm or less, about 78 nm or less, about 77 nm or less, about 76 nm or less, about 75 nm or less, about 74 nm or less, about 73 nm or less, about 72 nm or less, about 71 nm or less, about 69 nm or less, about 68 nm or less, about 6 It may be about 7 nm or less, about 66 nm or less, about 65 nm or less, about 64 nm or less, about 63 nm or less, about 62 nm or less, about 61 nm or less, about 59 nm or less, about 58 nm or less, about 57 nm or less, about 56 nm or less, about 55 nm or less, about 54 nm or less, about 53 nm or less, about 52 nm or less, about 51 nm or less, about 50 nm or less, about 49 nm or less, about 48 nm or less, about 47 nm or less, about 46 nm or less, or about 45 nm or less.

[0079] The effect of the reddening-resistant layer is maximized, and the physical properties mentioned above (thermal diffusion Rate In order to ensure a desired surface area ratio and / or reflectance (such as refractive index) and to maintain the transmittance, the location or distribution of voids within the void-containing layer (porous layer) may be controlled.

[0080] For example, the reddening-resistant layer or the void-containing layer (porous layer) has a scattering intensity logarithmic value of 0.06 nm in a graph of the scattering intensity of a small angle X-ray scattering (SAXS) analysis. -1 ~0.209nm -1 The scattering vector of the present invention may show at least one peak within the range of the scattering vector of the present invention. The above characteristic reflects the average distance of the voids. For example, a smaller scattering vector showing the above peak means that the average distance of the voids in the reddening-resistant layer or the void-containing layer (porous layer) tends to be longer, and a larger scattering vector means that the average distance of the voids in the reddening-resistant layer or the void-containing layer (porous layer) tends to be shorter.

[0081] The scattering vector is about 0.06 nm -1 If the vector is greater than or equal to 0.209 nm, the voids in the reddening-resistant layer or the void-containing layer (porous layer) are appropriately densely packed to block or reduce the applied heat. -1 If it is less than this, the voids are arranged at appropriate intervals in the reddening-resistant layer or void-containing layer (porous layer), and the surface roughness of the reddening-resistant layer or void-containing layer (porous layer) is maintained at an appropriate level, which makes it easier to apply the reddening-resistant layer or void-containing layer (porous layer) to an optical laminate. Furthermore, within the range of the scattering vector, the transmittance of the reddening-resistant layer can also be maintained within an appropriate range. In another example, the scattering vector at which the peak is confirmed is about 0.065 nm. -1 More than 0.07 nm -1 More than 0.075 nm -1 or more, about 0.08nm -1 or more, about 0.085nm -1 More than 0.09 nm -1 or more, about 0.095nm -1 or more than 0.1 nm -1 or more, and may be about 0.205 nm or more. -1 Below, approximately 0.2nm -1 Below, approximately 0.19nm -1 Below, approximately 0.185nm-1 Below, approximately 0.18nm -1 Less than or equal to 0.16 nm -1 It may be the following.

[0082] The peak is an extreme value or an inflection point where the log value of the scattering intensity appears upward in a graph of the log value of the scattering intensity confirmed by the analysis. The scattering vector is a value defined by the following Equation 5, and at least one peak may be confirmed within the range of the scattering vector.

[0083] [Formula 5] q=4πsin(θ / λ)

[0084] In Equation 5, q is the scattering vector, θ is a value that is ½ the scattering angle, and λ is the wavelength of the irradiated X-rays (unit: nm).

[0085] The mode of proceeding for the evaluation of small angle X-ray scattering is as described in the Examples herein.

[0086] The reddening-resistant layer or void-containing layer (porous layer) may satisfy the following mathematical formula 6, in which the value of A is 1.5 or less, the value of B is within the range of 0 to 0.01, and the value of C is within the range of 0 to 0.001.

[0087] [Formula 6]

number

[0088] In Equation 6, n(λ) is the refractive index of the reddening-resistant layer or the void-containing layer (porous layer) at a wavelength λ, where λ is any one of the wavelengths within the range of 300 to 1800 nm.

[0089] Equation 6 is obtained by fitting the ellipticity of the polarization measured by ellipsometry for the reddening-resistant layer or void-containing layer (porous layer) by the so-called Cauchy model. When the reddening-resistant layer or void-containing layer (porous layer) has values ​​of A, B, and C within the above-mentioned ranges that satisfy Equation 6, the reddening-resistant layer or void-containing layer (porous layer) may have void characteristics that can exhibit reddening resistance. Equation 6 reflects the refractive index characteristics exhibited by the reddening-resistant layer or void-containing layer (porous layer). The overall refractive index of the reddening-resistant layer or void-containing layer (porous layer) is determined by the refractive index of the voids that constitute the reddening-resistant layer or void-containing layer (porous layer) and the refractive index of other components other than the voids, such as the binder. Therefore, the values ​​of A, B and C in the formula 6 of the reddening-resistant layer or void-containing layer (porous layer) can reflect the amount of voids in the reddening-resistant layer. In one example, if the values ​​of A, B and / or C are within the above ranges, the voids in the reddening-resistant layer or void-containing layer (porous layer) are present at a level that can adequately block or delay the transfer of heat, and the roughness of the surface of the reddening-resistant layer or void-containing layer (porous layer) is maintained at an appropriate level, making it easier to apply the reddening-resistant layer or void-containing layer (porous layer) to an optical laminate. In addition, within the range of the values ​​of A, B and / or C, the transmittance of the reddening-resistant layer or void-containing layer (porous layer) in the optical laminate can be stably maintained.

[0090] In other examples, the value of A may be about 1.1 or more, about 1.15 or more, about 1.2 or more, about 1.25 or more, or about 1.3 or more. In other examples, the value of B may be about 0.0001 or more, about 0.0002 or more, about 0.0003 or more, about 0.0004 or more, about 0.0005 or more, about 0.0006 or more, or about 0.0007 or more, or about 0.009 or less, about 0.008 or less, about 0.007 or less, about 0.006 or less, about 0.005 or less, or about 0.004 or less. In other examples, the value of C may be about 0.000001 or more, about 0.000002 or more, about 0.000003 or more, about 0.000004 or more, about 0.000005 or more, about 0.000006 or more, about 0.000007 or more, about 0.000008 or more, about 0.000009 or more, about 0.00001 or more, about 0.00002 or more, about 0.00003 or more, about 0.00004 or more, about 0.00005 or more, about 0.00006 or about 0.00007 or more, or about 0.0009 or less, about 0.0008 or less, about 0.0007 or less, about 0.0006 or less, about 0.0005 or less, or about 0.0004 or less.

[0091] In the formula (6), λ is any one of wavelengths within the range of about 300 to about 1800 nm, and in one example, it may be about 400 nm or more or about 500 nm or more, or about 1700 nm or less, about 1600 nm or less, about 1500 nm or less, about 1400 nm or less, about 1300 nm or less, about 1200 nm or less, about 1100 nm or less, about 1000 nm or less, about 900 nm or less, about 800 nm or less, about 700 nm or less, or about 600 nm or less, or it may be in the wavelength range of about 550 nm. The reddening-resistant layer or void-containing layer (porous layer) satisfying the formula (6) may have a refractive index (based on a wavelength of 550 nm) of about 1.5 or less, and in another example, the refractive index may be about 1.1 or more or about 1.15 or more.

[0092] The volume fraction of the voids in the reddening-resistant layer or the void-containing layer (porous layer) may be about 0.1 or more. The volume fraction is the ratio of the volume of the space occupied by the voids when the total volume of the reddening-resistant layer or the void-containing layer (porous layer) is converted to 1. In this range, the reddening-resistant layer or the void-containing layer (porous layer) can appropriately block or reduce the transfer of heat. In addition, within the above range, the transmittance of the reddening-resistant layer or the void-containing layer (porous layer) in the optical laminate can be stably maintained. The volume fraction can be measured by confirming the density, mass, volume, etc. of the reddening-resistant layer or the void-containing layer (porous layer) through a buoyancy method, etc., or can be confirmed through the amount of hollow particles and the amount of binder applied when the reddening-resistant layer or the void-containing layer (porous layer) is formed using hollow particles, as described below.

[0093] The reddening-resistant layer or void-containing layer (porous layer) can be formed in various ways. A representative method for forming a void-containing layer is to apply hollow particles. Thus, in one embodiment, the reddening-resistant layer can include at least a binder and hollow particles.

[0094] The refractive index of the binder and the shell of the hollow particles, the size distribution of the hollow particles and the pores therein, the amount of the hollow particles, etc. are controlled to obtain the above-mentioned properties (thermal diffusion, Rate (Formula 4), surface characteristics (AFM surface area ratio), infrared reflectance, visible light transmittance, SAXS characteristics, volume fraction and / or refractive index characteristics) can be satisfied.

[0095] As the binder, various types may be applied without any particular limitation. For example, various curable resin compositions applicable for optical use may be applied as the binder. Examples of applicable optical resins include acrylic, epoxy and / or silicone resins, and the binder may be formed by applying the resin or a precursor capable of forming the resin. Such a resin or precursor may be curable, and may be, for example, a material that is cured by irradiation with light such as ultraviolet light or an electron beam, a material that is cured by heat, or a material that is cured by other action such as moisture.

[0096] The binder may have a refractive index (based on a wavelength of 550 nm) in the range of about 1.1 to 1.6. In this range of refractive index, the binder may be combined with hollow particles to easily form a reddening-resistant layer that satisfies the above-mentioned formula 6. In other examples, the refractive index may be about 1.15 or more, about 1.2 or more, about 1.25 or more, about 1.3 or more, about 1.35 or more, or about 1.4 or more, or about 1.55 or less, or about 1.5 or less.

[0097] A typical binder satisfying such a refractive index is an acrylic binder. The binder of the reddening-resistant layer may contain polymerized units of a polymerizable acrylic compound.

[0098] In one embodiment, the acrylic compound is an alkyl(meth)acrylate or alkoxy(meth)acrylate having an alkyl group or an alkoxy group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms; a monofunctional acrylate compound such as a hydroxyalkyl(meth)acrylate such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, or 8-hydroxyoctyl(meth)acrylate; 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentylglycol adipate di(meth)acrylate, hydroxypivalic acid, or the like. acid) neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified cyclopentenyl di(meth)acrylate, ethylene oxide-modified di(meth)acrylate, di(meth)acryloxyethyl isocyanurate, allyl-modified cyclohexyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, ethylene oxide-modified hexahydrophthalic acid di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, neopentyl glycol-modified trimethylpropane di(meth)acrylate, adamantane di(meth)acrylate or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc., such as bifunctional acrylates;Trifunctional acrylates such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, trifunctional urethane (meth)acrylate, or tris(meth)acryloxyethyl isocyanurate; diglycerol tetra(meth)acrylate or pentaerythritol tri(meth)acrylate; Tetrafunctional acrylates such as dipentaerythritol tetra(meth)acrylate; pentafunctional acrylates such as propionic acid modified dipentaerythritol penta(meth)acrylate; and hexafunctional acrylates such as dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, or urethane (meth)acrylate (e.g., a reaction product of an isocyanate monomer and trimethylolpropane tri(meth)acrylate) can be used.

[0099] The polyfunctional acrylate is a compound known in the art as a photocurable oligomer, and may be urethane acrylate, epoxy acrylate, polyester acrylate, polyether acrylate, etc. One or more suitable types of the above compounds may be selected and used.

[0100] The type of binder forming the reddening-resistant layer or the void-containing layer (porous layer) is not limited to the above, and various other optical materials may be used.

[0101] Combined with hollow particles to achieve the desired properties (thermal diffusion RateIn order to ensure appropriate void characteristics that satisfy the above-mentioned (Equation 4), surface characteristics (surface area ratio of AFM), infrared reflectance, visible light transmittance, SAXS characteristics, volume fraction and / or refractive index characteristics), the binder may be a multifunctional acrylate among the above-mentioned types. That is, the binder may include a polymer of the multifunctional acrylate. The multifunctional acrylate is a compound having at least two polymerizable functional groups (acryloyl group, methacryloyl group, acryloyloxy group or methacryloyloxy group). In other examples, the number of the acrylic polymerizable functional groups may be 3 or more, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less. As such a multifunctional acrylate, it is preferable to use a compound that does not have a hydroxy group and does not have a ring structure (e.g., an aromatic ring structure or a dicyclopentadiene structure), in order to improve thermal diffusion through the desired crosslinking degree and void characteristics. Rate (Formula 4), it is advantageous in forming a reddening-resistant layer that stably ensures surface characteristics (AFM surface area ratio), infrared reflectance, visible light transmittance, SAXS characteristics, volume fraction and / or refractive index characteristics. For the same reason, it is preferable that the binder of the reddening-resistant layer (void-containing layer (porous layer)) does not have the hydroxyl group or ring structure, or if it does, its ratio is limited. In addition, it is preferable to use a compound having a molecular weight in the range of about 150 to about 1,000 g / mol as the multifunctional acrylate, in order to achieve the desired degree of crosslinking and thermal diffusion through pore characteristics. Rate(Formula 4) is advantageous in forming a reddening-resistant layer in which the surface characteristics (AFM surface area ratio), infrared reflectance, visible light transmittance, SAXS characteristics, volume fraction and / or refractive index characteristics are stably ensured. In other examples, the molecular weight is about 170 g / mol or more, about 190 g / mol or more, about 210 g / mol or more, about 230 g / mol or more, about 250 g / mol or more, about 270 g / mol or more, or about 290 g / mol or more, or about 980 g / mol or less, about 960 g / mol or less, about 940 g / mol or less, about 920 g / mol or less, about 900 g / mol or less, about 880 g / mol or less, about 860 g / mol or less, about 840 g / mol or less, about 820 g / mol or less, about 800 g / mol or less, about 780 g / mol or less, about 760 g / mol or less, about 740 g / mol or less, about 720 g / mol or less. mol or less, about 700 g / mol or less, about 680 g / mol or less, about 660 g / mol or less, about 640 g / mol or less, about 620 g / mol or less, about 600 g / mol or less, about 580 g / mol or less, about 560 g / mol or less, about 540 g / mol or less, about 520 g / mol or less, about 500 g / mol or less, about 480 g / mol or less, about 460 g / mol or less, about 440 g / mol or less, about 420 g / mol or less, about 400 g / mol or less, about 380 g / mol or less, about 360 g / mol or less, about 340 g / mol or less, about 320 g / mol or less, or about 300 g / mol or less. From the viewpoint of more efficiently securing the target properties, the binder may substantially contain the multifunctional acrylate as a main component. Thus, the weight ratio of the multifunctional acrylate in the binder may be about 50% or more, about 52% or more, about 54% or more, about 56% or more, about 58% or more, about 60% or more, about 62% or more, about 64% or more, about 66% or more, about 68% or more, about 70% or more, about 72% or more, about 74% or more, about 76% or more, about 78% or more, about 80% or more, about 82% or more, about 84% or more, about 86% or more, about 88% or more, about 90% or more, about 92% or more, about 94% or more, about 96% or more, or about 98% or more, and this ratio may be about 100% or less or less than about 100%.The ratio is the ratio of the multifunctional acrylate in the binder, and for example, when the void-containing layer (porous layer) is a layer containing a binder and hollow particles, the ratio may be based on the total weight of the void-containing layer (porous layer) minus the weight of the hollow particles.

[0102] As the hollow particles, for example, particles having a specific particle size distribution can be used to satisfy each of the physical properties mentioned above. For example, as the hollow particles, particles having a D10 particle size in the range of about 20 nm to about 50 nm or about 25 nm to about 50 nm, particles having a D50 particle size in the range of about 55 nm to about 100 nm or about 50 nm to about 95 nm, and particles having a D90 particle size in the range of about 100 nm to about 200 nm or about 110 nm to about 180 nm in a weight cumulative curve of particle size distribution can be applied. In the above, the D10, D50, and D90 particle sizes are the particle size values ​​corresponding to about 10 wt%, about 50 wt%, and about 90 wt% of the maximum value (100 wt%) in a cumulative distribution graph showing the weight by particle size, assuming the total weight of the hollow particles to be 100 weight. By applying particles having the above particle size distribution, the desired reddening-resistant layer can be effectively formed.

[0103] In other examples, the D10 particle size may be about 21 nm or more, about 22 nm or more, about 23 nm or more, about 24 nm or more, about 25 nm or more, about 26 nm or more, about 27 nm or more, about 28 nm or more, about 29 nm or more, about 30 nm or more, about 31 nm or more, or about 32 nm or more, or about 49 nm or less, about 48 nm or less, about 47 nm or less, about 46 nm or less, about 45 nm or less, about 44 nm or less, about 43 nm or less, about 42 nm or less, about 41 nm or less, about 40 nm or less, about 39 nm or less, about 38 nm or less, about 37 nm or less, about 36 nm or less, about 35 nm or less, about 34 nm or less, or about 33 nm or less.

[0104] In other examples, the D50 particle size may be about 56 nm or more, about 57 nm or more, about 58 nm or more, about 59 nm or more, about 60 nm or more, about 61 nm or more, or about 62 nm or more, or about 99 nm or less, about 98 nm or less, about 97 nm or less, about 96 nm or less, about 95 nm or less, about 94 nm or less, about 93 nm or less, about 92 nm or less, about 91 nm or less, about 90 nm or less, about 89 nm or less, about 88 nm or less, about 87 nm or less, about 86 nm or less, about 85 nm or less, about 84 nm or less, about 83 nm or less, about 82 nm or less, about 81 nm or less, about 79 nm or less, about 78 nm or less, about 77 nm or less, about 76 nm or less, about 75 nm or less, about 74 nm or less, about 73 nm or less, about 72 nm or less, about 71 nm or less, or about 70 nm or less.

[0105] In other examples, the D90 particle size is about 111 nm or more, about 112 nm or more, about 113 nm or more, about 114 nm or more, about 115 nm or more, about 116 nm or more, about 117 nm or more. Above, about 118 nm or more, about 119 nm or more, about 120 nm or more, about 121 nm or more, about 122 nm or more, or about 123 nm or more, or about 179 nm or less, about 178 nm or less, about 177nm or less, about 176nm or less, about 175nm or less, about 174nm or less, about 173nm or less, about 172nm or less, about 171nm or less, about 170nm or less, about 169nm or less , about 168 nm or less, about 167 nm or less, about 166 nm or less, about 165 nm or less, about 164 nm or less, about 163 nm or less, about 162 nm or less, about 161 nm or less, about 160 nm or less or less, about 159 nm or less, about 158 ​​nm or less, about 157 nm or less, about 156 nm or less, about 155 nm or less, about 154 nm or less, about 153 nm or less, about 152 nm or less, about 151 nm or less, about 150 nm or less, about 149 nm or less, about 148 nm or less, about 147 nm or less, about 146 nm or less, about 145 nm or less, about 144 nm or less, about 143 nm or less, about 142 nm or less, about 141 nm or less, about 140 nm or less, about 139 nm or less, about 138 nm or less, about 137 nm or less, about 136 nm or less, about 135 nm or less, about 134 nm or less, about 133 nm or less, about 132 nm or less, about 131 nm or less, about 130 nm or less, about 129 nm or less, about 128 nm or less, about 127 nm or less, or about 126 nm or less.

[0106] The hollow particles may be particles whose pore size corresponds to the size of the voids, and therefore the pore size may be within a range of about 0.5 nm to about 100 nm.

[0107] In other examples, the size of the pores is about 1 nm or more, about 2 nm or more, about 3 nm or more, about 4 nm or more, about 5 nm or more, about 6 nm or more, about 7 nm or more, about 8 nm or more, about 9 nm or more, about 10 nm or more, about 11 nm or more, about 12 nm or more, about 13 nm or more, about 14 nm or more, about 15 nm or more, about 16 nm or more, about 17 nm or more, about 18 nm or more, about 19 nm or more, about 20 nm or more, about 21 nm or more, about 22 nm or more. or greater than about 23 nm, greater than about 24 nm, greater than about 25 nm, greater than about 26 nm, greater than about 27 nm, greater than about 28 nm, greater than about 29 nm, greater than about 31 nm, greater than about 32 nm, greater than about 33 nm, greater than about 34 nm, greater than about 35 nm, greater than about 36 nm, greater than about 37 nm, or greater than about 38 nm; or less than about 99 nm, less than about 98 nm, less than about 97 nm, less than about 96 nm, less than about 95 nm, less than about 94 nm, less than about 93 nm, less than about 92nm or less, about 91nm or less, about 90nm or less, about 89nm or less, about 88nm or less, about 87nm or less, about 86nm or less, about 85nm or less, about 84nm or less, about 83nm or less, about 82nm or less, about 81nm Below, about 79 nm or less, about 78 nm or less, about 77 nm or less, about 76 nm or less, about 75 nm or less, about 74 nm or less, about 73 nm or less, about 72 nm or less, about 71 nm or less, about 69 nm or less, about 68 nm or less, about 6 It may be about 7 nm or less, about 66 nm or less, about 65 nm or less, about 64 nm or less, about 63 nm or less, about 62 nm or less, about 61 nm or less, about 59 nm or less, about 58 nm or less, about 57 nm or less, about 56 nm or less, about 55 nm or less, about 54 nm or less, about 53 nm or less, about 52 nm or less, about 51 nm or less, about 50 nm or less, about 49 nm or less, about 48 nm or less, about 47 nm or less, about 46 nm or less, or about 45 nm or less.

[0108] The hollow particles have the above-mentioned characteristics and, together with the binder, have the above-mentioned characteristics (thermal diffusion Rate(Formula 4), surface characteristics (surface area ratio of AFM), infrared reflectance, visible light transmittance, SAXS characteristics, volume fraction and / or refractive index characteristics) can be applied to various types of materials without any particular limitation.

[0109] For example, the hollow particles may be organic particles whose shell portion is made of an organic substance, inorganic particles made of an inorganic substance, and / or organic / inorganic particles made of an organic / inorganic substance, etc. Examples of such particles include acrylic particles such as PMMA (poly(methyl methacrylate)), epoxy particles, nylon particles, styrene particles and / or styrene / vinyl monomer copolymer particles, etc., and inorganic particles such as silica particles, alumina particles, indium oxide particles, tin oxide particles, zirconium oxide particles, zinc oxide particles and / or titania particles, etc., but are not limited thereto.

[0110] The reddening-resistant layer or void-containing layer (porous layer) may contain the hollow particles at a ratio of about 5% by weight or more. In other examples, the ratio may be about 10% by weight or more, about 15% by weight or more, about 20% by weight or more, about 25% by weight or more, about 30% by weight or more, about 35% by weight or more, about 40% by weight or more, about 45% by weight or more, about 50% by weight or more, about 55% by weight or more, about 60% by weight or more, about 65% by weight or more, about 70% by weight or more, about 75% by weight or more, about 80% by weight or more, about 85% by weight or more, about 90% by weight or more, about 95% by weight or more, It can be about 100% by weight or more, about 105% by weight or more, about 110% by weight or more, about 115% by weight or more, about 120% by weight or more, about 125% by weight or more, about 130% by weight or more, about 135% by weight or more, about 140% by weight or more, about 145% by weight or more, about 150% by weight or more, about 155% by weight or more, about 160% by weight or more, about 165% by weight or more, about 170% by weight or more, about 175% by weight or more, or about 180% by weight or more. In other examples, the ratio may be about 9,000% by weight or less, about 8,000% by weight or less, about 7,000% by weight or less, about 6,000% by weight or less, about 5,000% by weight or less, about 4,000% by weight or less, about 3,000% by weight or less, about 2,000% by weight or less, about 1,000% by weight or less, about 900% by weight or less, about 800% by weight or less, about 700% by weight or less, about 600% by weight or less, about 500% by weight or less, about 400% by weight or less, about 300% by weight or less, about 250% by weight or less, about 240% by weight or less, about 230% by weight or less, about 220% by weight or less, about 210% by weight or less, or about 200% by weight or less.

[0111] The ratio of the hollow particles can be adjusted according to the desired properties. In one embodiment, the reddening-resistant layer or the void-containing layer (porous layer) can include only hollow particles as particles. That is, in this embodiment, the reddening-resistant layer or the void-containing layer (porous layer) does not need to include so-called solid particles. This allows the desired properties of the reddening-resistant layer or the void-containing layer (porous layer) to be more appropriately realized.

[0112] In addition to the above components, the reddening-resistant layer or void-containing layer (porous layer) may contain any additives known in the art, if necessary, such as a curing agent or initiator for the binder, an antioxidant, an ultraviolet stabilizer, an ultraviolet absorber, a toning agent, an antifoaming agent, a surfactant, and / or a plasticizer.

[0113] The thickness of the reddening-resistant layer or the void-containing layer (porous layer) can be controlled to achieve the desired reddening resistance. For example, the reddening-resistant layer or the void-containing layer (porous layer) may have a thickness of about 200 nm or more. In such a thickness range, the desired reddening resistance can be effectively achieved. In other examples, the thickness may be about 250 nm or more, about 300 nm or more, about 350 nm or more, about 400 nm or more, about 450 nm or more, about 500 nm or more, about 550 nm or more, about 600 nm or more, about 650 nm or more, about 700 nm or more, about 750 nm or more, about 800 nm or more, about 850 nm or more, or about 900 nm or more. The upper limit of the thickness is not particularly limited. Usually, the thicker the reddening-resistant layer, the better the effect of preventing, mitigating, reducing, suppressing, and / or delaying heat. Therefore, the upper limit of the thickness of the reddening-resistant layer or void-containing layer (porous layer) is not particularly limited, and may be selected in consideration of the thickness required for the optical laminate, etc., as long as the heat prevention, mitigation, reduction, suppression and / or delay effect is ensured. In one example, the thickness of the reddening-resistant layer or void-containing layer (porous layer) may be about 3,000 nm or less, about 2,900 nm or less, about 2,800 nm or less, about 2,700 nm or less, about 2,600 nm or less, about 2,500 nm or less, about 2,400 nm or less, about 2,300 nm or less, about 2,200 nm or less, about 2,100 nm or less, about 2,000 nm or less, or about 1,950 nm or less.

[0114] The location of the reddening resistant layer within the optical stack can also be controlled to ensure desired reddening resistance performance.

[0115] The reddening-resistant layer may be a layer separately included in the optical laminate, or may be a layer realized by forming voids in a layer (eg, an adhesive layer or a pressure-sensitive adhesive layer) already present in the optical laminate.

[0116] The location of the anti-reddening layer within the optical stack may be controlled for the purpose, i.e., to prevent, mitigate, reduce, inhibit and / or delay reddening.

[0117] For example, the reddening-resistant layer can be located as close as possible to the optically functional layer that is the main cause of reddening in the optical stack. That is, the distance between the reddening-resistant layer and the optically functional layer in the optical stack can be controlled. The distance can be the minimum distance, the maximum distance, or the average distance between the opposing surfaces of the reddening-resistant layer and the optically functional layer. In one example, the distance between the reddening-resistant layer and the optically functional layer may be within about 90 μm, within about 85 μm, within about 80 μm, within about 75 μm, within about 70 μm, within about 65 μm, within about 60 μm, within about 55 μm, within about 50 μm, within about 45 μm, within about 40 μm, within about 35 μm, within about 30 μm, within about 25 μm, within about 20 μm, within about 15 μm, within about 10 μm, within about 5 μm, within about 1 μm, within about 0.9 μm, within about 0.8 μm, within about 0.7 μm, within about 0.6 μm, within about 0.5 μm, within about 0.4 μm, within about 0.3 μm, or within about 0.2 μm. The optical functional layer and the reddening-resistant layer are located closest to each other when the two layers are in contact with each other, and in this case, the distance is 0 μm. Therefore, the lower limit of the distance is 0 μm. In other examples, the distance may be about 0.01 μm or more, about 0.02 μm or more, about 0.03 μm or more, about 0.04 μm or more, about 0.05 μm or more, about 0.09 μm or more, or about 0.1 μm or more.

[0118] Such a reddening-resistant layer may be disposed at a position that does not form the outermost surface of the optical laminate. That is, the reddening-resistant layer does not have to be the outermost layer of the optical laminate. Setting such a position may be required to exhibit the reddening-resistant properties of the optical laminate and / or the optical functional layer.

[0119] In another example, the optical laminate may include an additional layer together with the reddening-resistant layer and the optical functional layer, and the reddening-resistant layer may be located between the optical functional layer and the additional layer. Figure 1 shows an example of such a layer structure, in which the additional layer 30, the reddening-resistant layer 20 and the optical functional layer 10 are formed in sequence. The additional layer may be a protective film, a pressure-sensitive adhesive layer, an adhesive layer, a hard coat layer, an anti-reflection layer, a retardation layer, a brightness improvement layer, or the like, or a cover glass, which will be described later, but is not limited thereto.

[0120] The optical laminate of the present application can show a somewhat high surface reflectance by the above-mentioned arrangement. That is, the reddening-resistant layer of the present application can act to reduce the reflectance due to its configuration, but since such a reddening-resistant layer does not exist on the surface, the surface reflectance of the optical functional layer can be formed somewhat high unless a separate anti-reflection layer or the like is formed. For example, the optical laminate can have a reflectance of about 2% or more. The reflectance can be a reflectance for light in the visible light region, for example, any one wavelength within the range of about 380 nm to 780 nm, or a wavelength of a certain region within the range, or the entire region, or an average reflectance. In other examples, the reflectance can be about 2.5% or more, about 3% or more, about 3.5% or more, or about 4% or more, or about 10% or less, about 9% or less, about 8% or less, about 7% or less, about 6% or less, or about 5% or less.

[0121] The above-mentioned arrangement can effectively prevent, mitigate, reduce, suppress and / or delay the reddening phenomenon of the optical functional layer and / or the optical laminate.

[0122] The optical laminate may also include a variety of different layers, so long as it basically includes the reddening-resistant layer and the optically functional layer.

[0123] Examples of such a layer include a protective film for the optical laminate, a pressure-sensitive adhesive layer, an adhesive layer, a retardation film, a hard coat layer, or a low-reflection layer. The layer may be the additional layer described above.

[0124] The type of the additional layer may be a general structure known in the art. For example, the protective film may be a resin film having excellent transparency, mechanical strength, thermal stability, moisture barrier property, or isotropy. Examples of such films include cellulose resin films such as triacetyl cellulose (TAC) film, polyester films, polyethersulfone films, polysulfone films, polycarbonate films, polyamide films, polyimide films, polyolefin films, acrylic films, cyclic polyolefin films such as norbornene resin films, polyarylate films, polystyrene films, and polyvinyl alcohol films. In addition to the protective layer in the form of a film, a cured resin layer obtained by curing a heat- or light-curable resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone resin may be applied to the protective film. Such a protective film may be formed on one or both sides of the optical functional layer.

[0125] As the retardation film, a general material may be applied, for example, a uniaxially or biaxially stretched birefringent polymer film, an oriented film of a liquid crystal polymer, a polymerized layer of a polymerizable liquid crystal compound, etc. The thickness of the retardation film is not particularly limited.

[0126] The protective film or retardation film described above can be attached to the optical functional layer or the like by an adhesive or the like, and such protective film or the like may be subjected to an adhesion-facilitating treatment such as a corona treatment, a plasma treatment, a primer treatment, a saponification treatment, etc. In addition, when the protective film is attached to the optical functional layer or the reddening-resistant layer, a hard coat layer, a low reflection layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, a haze layer, or the like may be present on the surface of the protective film opposite to the surface attached to the optical functional layer or the reddening-resistant layer.

[0127] In addition to the protective film or retardation film, the optical laminate may contain various elements such as a reflector or a semi-transmitting plate, and the types of elements are not particularly limited.

[0128] An adhesive may be used to bond each layer of the optical laminate. Examples of the adhesive include, but are not limited to, an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin-based adhesive, a vinyl-based latex-based adhesive, or a water-based polyester. A water-based adhesive may be generally used as the adhesive, but a solvent-free photocurable adhesive may also be used depending on the type of film to be attached.

[0129] The optical laminate may include a pressure-sensitive adhesive layer for adhesion to other members such as a liquid crystal panel or a cover glass. The pressure-sensitive adhesive forming the pressure-sensitive adhesive layer is not particularly limited, and may be appropriately selected and used, for example, from those having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, or a fluorine-based or rubber-based polymer as a base polymer. A release film may be temporarily attached to cover the exposed surface of such a pressure-sensitive adhesive layer for the purpose of preventing contamination or the like until it is put into practical use.

[0130] Such an optical laminate may have various types of structures. For example, FIG. 2 shows a structure in which the reddening-resistant layer 20 is introduced into the structure of a polarizing plate, which is the most basic optical laminate. That is, a basic polarizing plate has a structure in which a protective film 301 is attached to at least one surface of a polarizing layer 100, and the reddening-resistant layer 20 may be located between the polarizing layer 100 and the protective film 301. In the structure of FIG. 2, an adhesive or a pressure-sensitive adhesive may be used to bond each of the layers 100, 20, and 301. In one example, the reddening-resistant layer 20 in FIG. 2 may be a separate layer or may be the adhesive or pressure-sensitive adhesive itself. That is, hollow particles or the like may be introduced into the adhesive or pressure-sensitive adhesive to form a void-containing layer (porous layer) to function as a reddening-resistant layer.

[0131] 2, a protective film 302 is attached to the lower part of the polarizing layer 100, i.e., the surface opposite to the reddening-resistant layer 20, but this protective film 302 may be omitted or may be another type of layer (for example, the above-mentioned retardation film or cured resin layer). For example, an adhesive layer may be formed on the lower part of the protective film 302 present on the surface opposite to the reddening-resistant layer 20, i.e., the surface of the protective film 302 opposite to the surface on the polarizing layer 100 side, or an adhesive layer may be formed instead of the protective film 302.

[0132] 3 shows a modified structure in which two protective films 301, 302 are present on one side of the polarizing layer 100, and the reddening-resistant layer 20 is present between the protective films 301, 302. In this case, the layers may be bonded with an adhesive or a glue, and the reddening-resistant layer 20 may be an adhesive or a glue. In this structure, the matters regarding the protective film 303 present below the polarizing layer 100 are the same as those in the case of the protective film 302 present below the polarizing layer 100 in the structure of FIG. 2.

[0133] The structures of FIGS. 2 and 3 are merely examples of the present application, and the optical laminate of the present application may be configured in a variety of other structures.

[0134] The present application also relates to a display device including the optical laminate. The type of the display device may be various without particular limitation, for example, a known LCD (Liquid Crystal Display) or OLED (Organic Light Emitting Display), and the optical laminate may be applied in a conventional manner in such a display device.

[0135] In particular, the optical stack is effectively applied to display devices including a so-called cover glass.

[0136] Such a device usually includes a cover glass and an optical laminate attached to the cover glass by so-called OCA (Optical Clear Adhesive) or OCR (Optical Clear Resin), and the laminate of the present application can be applied as the optical laminate. Thus, the display device includes a cover glass and an optical laminate attached to the cover glass, and the optical laminate can include the optical functional layer and a reddening-resistant layer formed on at least one surface of the optical functional layer, and in this case, the reddening-resistant layer can be located between the cover glass and the optical functional layer.

[0137] Generally, a display device including a cover glass is used for applications such as vehicle navigation systems. In this case, the reddening phenomenon becomes even more problematic due to the cover glass having high thermal conductivity.

[0138] However, the optical laminate of the present application can be applied to a device having the above structure to solve the above problems.

[0139] The specific structure of the display device is not particularly limited, and may follow any known structure, so long as the optical laminate of the present application is applied. Effect of the Invention

[0140] The present application makes it possible to provide an optical laminate or a reddening-resistant layer applied thereto that does not induce the so-called reddening phenomenon even when driven or maintained under very harsh conditions (e.g., very high temperature conditions). [Brief description of the drawings]

[0141]

Figure 1

Figure 2

Figure 3

[0142] The polarizing layer and the like will be described in more detail below through examples of the present application, but the scope of the present application is not limited to the following.

[0143] In the following, the physical properties of the polarizing layer and the like were measured by the following methods.

[0144] 1. Thickness measurement The thickness of the polarizing layer and the reddening-resistant layer can be measured by applying a TEM (Transmission Electron Microscopy) device. After taking a cross-section of the polarizing layer or the reddening-resistant layer with the TEM device, the thickness of the layer can be confirmed from the taken image. In this embodiment, the TEM device used is Hitachi's H-7650 product.

[0145] 2. Measurement of particle size distribution and pore size of hollow particles The particle size distribution of the hollow particles was measured using an ELSZ-2000 device manufactured by Otsuka Electronics. The particle diameter and pore size of the hollow particles were measured using a TEM (Transmission Electron Microscopy) device. In this embodiment, the TEM device was used as the Hitachi H-7650 product. The particle diameter and pore size were measured by photographing (at a magnification of 10,000 times) the cross section of the reddening-resistant layer in the optical laminate (polarizing plate) manufactured in the embodiment using the TEM device, and then arbitrarily selecting 50 hollow particles to determine the particle diameter and pore size of each, and the arithmetic average was used as the representative value of the particle diameter and pore size.

[0146] 3. Measurement of CIE color coordinates The color coordinates were measured using a JASCO V-7100 spectrophotometer. The JASCO V-7100 spectrophotometer measures the color coordinates (TD color coordinates) at the point where the transmittance is minimum by rotating the absorption axis of the polarizer built into the instrument from 0 degrees to 360 degrees, and measures the color coordinates (MD color coordinates) by further rotating the absorption axis of the polarizer to be measured 90 degrees clockwise at the point where the transmittance is minimum, and then derives a representative value of the color coordinates based on each measurement value. The color coordinates described in the examples of this specification are color coordinates confirmed by the JASCO V-7100 spectrophotometer.

[0147] 4. Measurement of transmittance and reflectance The single transmittance of the polarizing plate was measured using a JASCO V-7100 spectrophotometer. The JASCO V-7100 spectrophotometer is an instrument that measures the transmittance of the polarizing plate within a wavelength range of 380 to 780 nm to derive a representative value for the wavelength range. In this embodiment, the transmittance measured by the JASCO V-7100 spectrophotometer is described.

[0148] 5. Measurement of the weight ratio of potassium K and zinc Zn in the polarizing layer The weight ratio of potassium K and zinc Zn in the polarizing layer was measured in the following manner: First, 0.1g of the polarizing layer was dissolved in nitric acid solution (2mL) with a concentration of about 65% by weight at room temperature (about 25℃), and then diluted to 40mL with water (deionized water).The weights of potassium K and zinc Zn in the polarizing layer were measured using ICP-OES (Optima 5300).

[0149] 6. Thermal diffusion of reddening-resistant layer Rate Evaluation Thermal diffusion of reddening-resistant layer RateThe thermal diffusion coefficient was measured by the following method. The thermal diffusion coefficient was measured by the method described in the following Example, in a state where a reddening-resistant layer was formed on a TAC (Triacetyl cellulose) film (PG601F, manufactured by Hyosung Co., Ltd.) having a thickness of about 60 μm. Rate The thickness of the reddening-resistant layer is described in each example. Graphite coating was performed on the upper and lower surfaces of the TAC film / reddening-resistant layer laminate. The graphite coating was formed using a GRAPHITE product from CRAMLIN. This product is capable of graphite coating using a spray method, and the product was sprayed once on the upper surface (reddening-resistant layer surface) and the lower surface (TAC film) of the laminate, and then dried to form a graphite layer. Then, a thermal diffusion test was performed using a LFA 457 MicroFlash product from NETZSCH. Rate The thermal diffusion Rate The temperature was measured at 95℃ and confirmed by checking whether the heat was transferred from one graphite surface to another. Rate The thermal diffusion of the laminate with respect to the TAC film was evaluated in the examples. Rate The relative proportions are given.

[0150] 7. Evaluation of infrared reflectance of reddening-resistant layer The infrared reflectance of the reddening-resistant layer was confirmed by the following method. The infrared reflectance was evaluated in a state where the reddening-resistant layer was formed on a TAC (Triacetyl cellulose) film having a thickness of about 60 μm by the method described in the following examples. In this case, the thickness of the reddening-resistant layer is described in each example. A black tape (TOMOEGAWA) was attached to the lower surface (the surface of the film on which the reddening-resistant layer is not formed) of the TAC film of the reddening-resistant layer / TAC film laminate to perform a darkening treatment, and the average reflectance in the wavelength range of 800 to 1300 nm was measured in reflectance mode using a Solidspec 3700 device from SHIMADZU. Using this device, the reflectance for a wavelength range of 1 nm intervals within the range of 800 nm to 1300 nm can be confirmed, and in this example, the arithmetic average value of the reflectance for each wavelength was used as the representative value of the infrared reflectance.

[0151] 8. Evaluation of reddening-resistant layer by small angle X-ray scattering (SAXS) The evaluation of small angle X-ray scattering of the reddening-resistant layer was carried out in the following manner. The evaluation was carried out in a state where the reddening-resistant layer was formed on a TAC (Triacetyl cellulose) film having a thickness of about 60 μm in the manner described in the following examples. In this case, the thickness of the reddening-resistant layer is described in each example. The laminate of the TAC film / reddening-resistant layer was cut to have a horizontal and vertical dimension of about 1 cm, respectively, to prepare a test piece. The reddening-resistant layer of the test piece was irradiated with X-rays having a wavelength of 0.0733 nm at a distance of 4 m to obtain the scattering intensity according to the scattering vector. The measurement was carried out at the 4C beamline of the Pohang Accelerator, and X-rays having a vertical size of about 0.023 mm and a horizontal size of about 0.3 mm were used. A 2D mar CCD was used as a detector. After obtaining an image of the scattered 2D diffraction pattern, this was calibrated using the sample-to-detector distance obtained through a standard sample (polyethylene-block-polybutadiene-block-polystyrene, SEBS), and the scattering intensity was converted by the scattering vector (q) through circular averaging. In this case, the scattering vector was calculated by the following formula A.

[0152] [Formula A] q=4πsin(θ / λ)

[0153] In formula A, q is the scattering vector, θ is a value that is half the scattering angle (unit: degree), and λ is the wavelength of the irradiated X-ray (unit: angstrom (Å)).

[0154] 9. Measurement of Cauchy Parameters The refractive index and Cauchy parameters of the reddening-resistant layer were measured in the following manner. The evaluation was performed in a state where the reddening-resistant layer was formed on a TAC (Triacetyl cellulose) film having a thickness of about 60 μm in the manner described in the following examples. The thickness of the reddening-resistant layer is described in each example. The characteristics were evaluated for the reddening-resistant layer of the laminate (reddening-resistant layer / TAC film) using an equipment (JA Woollam Co. M-2000). The equipment was applied to the reddening-resistant layer, and linear polarization was measured in the wavelength range of 380 nm to 1,000 nm under the condition of an incident angle of 70 degrees. The measured linear polarization data (Ellipsometry data (Psi(Ψ), delta(Δ))) was optimized (fitted) using Complete EASE software so that the MSE of the Cauchy model of the following general formula 1 was 25 or less, and n(λ), A, B, and C of the following formula 6 were obtained. The Roughness function was applied as on (range -20~50 nm) during the optimization process.

[0155] [Formula 6]

number

[0156] In Equation 6, n(λ) is the refractive index at a wavelength of λ nm.

[0157] 10.Evaluation of surface area ratio The surface area ratio of the reddening-resistant layer (void-containing layer (porous layer)) was measured using an AFM device (Atomic Force Microscope, Park Systems, XE7). As described in the Examples, a laminate having a reddening-resistant layer (void-containing layer (porous layer)) formed on one side of a TAC film was cut to a width and length of 1 cm to prepare a sample, which was then fixed to the stage of the device using carbon tape and subjected to measurement. A PPP-NCHR 10 (Force Constant: 42 N / m, Resonance Frequency 330 kHz) was used as a tip for measurement. The measurement conditions were as follows.

[0158] <Measurement conditions> x-scan size: 1μm y-scan size: 1μm Scan rate: 0.7~1Hz Z Servo Gain:1 Set Point: 10~15nm

[0159] The data measured under the above conditions was smoothed under the following conditions using the XEI program.

[0160] <Flattening conditions> Scope: Line Orientation: X and Y axis Regression Order:1

[0161] After planarization, the surface area ratios were extracted in the Region tab within the XEI program.

[0162] Production Example 1. Production of Polarizing Layer (A) A PVA (poly(vinyl alcohol)) film (M3004L, Nippon Gosei Co., Ltd.) with a thickness of approximately 30 μm was immersed in iodine I. 2The film was dyed by immersing it in a dyeing solution at 28° C. containing 0.2% by weight of boron and 2.5% by weight of potassium iodide KI for 60 seconds. The dyed PVA film was then crosslinked by immersing it in an aqueous solution (crosslinking solution) at 35° C. containing 1% by weight of boron and 3% by weight of potassium iodide KI for 60 seconds. The crosslinked PVA film was then stretched at a stretch ratio of 5.4 times using a roll-to-roll stretching method. The stretched PVA film was washed by immersing it in ion-exchanged water at 25° C. for 60 seconds, and then immersed in an aqueous solution at 25° C. containing 2% by weight of zinc nitrate and 5% by weight of potassium iodide KI for 30 seconds. The PVA film was then dried at a temperature of 80° C. for 60 seconds to produce a PVA polarizing layer. The final thickness of the polarizing layer produced was about 12 μm, the potassium content was about 0.9% by weight, and the zinc content was about 0.3% by weight. In addition, 1 / (1+0.025d / R) was approximately 0.9, where d is the thickness of the polarizing layer (12 μm) and R is the ratio K / Zn of the weight ratio K (unit: weight) of the potassium component contained in the polarizing layer to the weight ratio Zn (unit: weight) of the zinc component.

[0163] Production Example 2. Production of polarizing layer (B) A polarizing layer was manufactured using a PVA (poly(vinyl alcohol)) film (M4504L, Nippon Gosei Co., Ltd.) with a thickness of about 45 μm as a disk film. First, a swelling treatment was performed on the disk film. The swelling treatment was performed by immersing the disk film in pure water at a temperature of 25° C. for 30 seconds. During the swelling treatment, the film was stretched to about 28% of the final stretch ratio. Next, iodine I was added to the pure water. 2The dyeing process was carried out using a dyeing solution in which boron and potassium iodide KI were dissolved at concentrations of about 0.2% by weight and 2.5% by weight, respectively. The dyeing process was carried out by immersing the disk film in the dyeing solution at 28°C for about 2 minutes. In this process, the stretching was carried out so that the film was stretched to about 40% of the final stretching ratio. After that, the dyed PVA film was immersed in an aqueous solution (crosslinking solution) containing 1% by weight of boron and 3% by weight of potassium iodide at 35°C for 60 seconds to carry out a crosslinking process. Next, the disk film was stretched. The stretching was carried out in an aqueous solution (treatment solution) containing about 3% by weight of boric acid and potassium iodide. The temperature of the treatment solution was about 50°C. Next, the stretched film was washed with an aqueous solution. At this time, the temperature of the aqueous solution was about 25°C, and the washing process was carried out within 1 minute. After that, the film was dried to produce a PVA polarizing layer (thickness: 27 μm, total stretching ratio: 5.4 times).

[0164] Manufacturing Example 3. Manufacturing of material for reddening-resistant layer (A) The reddening-resistant layer was manufactured by applying TMPTA (trimethylolpropane triacrylate) as a binder and hollow silica particles. The hollow silica particles used had D10, D50 and D90 particle sizes of 32.1 nm, 62.6 nm and 123.4 nm, respectively. In this case, the average pore size measured by TEM after forming the reddening-resistant layer was about 38.3 nm, and the particle diameter was about 53 nm. The binder, the hollow silica particles, a fluorine-containing compound (RS-90, DIC) and an initiator (Irgacure 127, Ciba) were diluted in a solvent MIBK (methyl isobutyl ketone) in a weight ratio of 31:65:0.1:3.9 (binder: hollow silica particles: fluorine-containing compound: initiator) based on the solid content to manufacture a coating liquid.

[0165] Manufacturing Example 4. Manufacturing of Reddish-Resistant Layer (B) Material The reddening-resistant layer was manufactured by applying TMPTA (trimethylolpropane triacrylate) as a binder and hollow silica particles. The hollow silica particles used had D10, D50 and D90 particle sizes of 39.9 nm, 70.6 nm and 126.0 nm, respectively. In this case, the average pore size measured by TEM after forming the reddening-resistant layer was about 44.1 nm, and the particle diameter was about 61 nm. The binder, the hollow silica particles, a fluorine-containing compound (RS-90, DIC) and an initiator (Irgacure 127, Ciba) were diluted in a solvent MIBK (methyl isobutyl ketone) in a weight ratio of 55.1:40:1.1:3.8 (binder: hollow silica particles: fluorine-containing compound: initiator) to manufacture a coating liquid.

[0166] Manufacturing Example 5. Manufacturing of Reddish-Resistant Layer (C) Material The reddening-resistant layer was manufactured by applying PETA (Pentaerythritol triacrylate) as a binder and hollow silica particles. The hollow silica particles had D10, D50 and D90 particle sizes of 39.9 nm, 70.6 nm and 126.0 nm, respectively. In this case, the average pore size measured by TEM after forming the reddening-resistant layer was about 44.1 nm, and the particle diameter was about 61 nm. The binder, the hollow silica particles, a fluorine-containing compound (RS-90, DIC) and an initiator (Irgacure 127, Ciba) were diluted in a weight ratio of 76.5:20:0.5:3.0 (binder: hollow silica particles: fluorine-containing compound: initiator) with a solvent MIBK (methyl isobutyl ketone) to manufacture a coating liquid.

[0167] Manufacturing Example 6. Manufacturing of material for reddening-resistant layer (D) The reddening-resistant layer was manufactured by applying PETA (Pentaerythritol triacrylate) as a binder and hollow silica particles. The hollow silica particles used had D10, D50 and D90 particle sizes of 39.9 nm, 70.6 nm and 126.0 nm, respectively. In this case, the average pore size measured by TEM after forming the reddening-resistant layer was about 44.1 nm, and the particle diameter was about 61 nm. The binder, the hollow silica particles, a fluorine-containing compound (RS-90, DIC) and an initiator (Irgacure 127, Ciba) were diluted in a weight ratio of 86.5:10:0.5:3.0 (binder: hollow silica particles: fluorine-containing compound: initiator) with a solvent MIBK (methyl isobutyl ketone) to manufacture a coating liquid.

[0168] Production Example 7. Production of resin layer (A) material A resin layer material was prepared by applying PETA (Pentaerythritol triacrylate) as a binder and solid silica particles instead of hollow particles. The solid silica particles used had D10, D50 and D90 particle sizes of 43.1 nm, 69.9 nm and 125.8 nm, respectively. In this case, the particle diameter measured by TEM after forming the resin layer was about 60 nm. The binder, the solid silica particles, a fluorine-containing compound (RS-90, DIC) and an initiator (Irgacure 127, Ciba) were diluted in a weight ratio of 31:65:0.1:3.9 (binder: solid silica particles: fluorine-containing compound: initiator) with a solvent of MIBK (methyl isobutyl ketone) to prepare a coating liquid.

[0169] Example 1. A typical optical water-based adhesive layer (thickness: 100 nm) was applied to the polarizing layer (A) obtained in Production Example 1, and a COP (Cycloolefin Polymer) film (manufacturer: Zeon) with a thickness of about 30 μm was attached as a protective film. Separately, a reddening-resistant layer was formed on a TAC (Triacetyl cellulose) film (Hyosung) with a thickness of about 60 μm. The reddening-resistant layer was formed by coating the material for the reddening-resistant layer (A) of Production Example 3 with a Mayer bar, drying at about 60°C for about 1 minute, and then irradiating it with ultraviolet light (252 mJ / cm2). 2 ) to form a final thickness of about 450 nm. The surface area ratio (Surface Area Ratio) measured for the surface opposite to the surface in contact with the TAC film of the formed reddening-resistant layer was about 0.148. Next, the reddening-resistant layer of the laminate of the reddening-resistant layer and the TAC film was attached to the polarizing layer (A) of the laminate of the COP film and the polarizing layer (A) produced above with the same water-based adhesive (thickness: 100 nm). Next, an acrylic adhesive layer was formed on the bottom of the polarizing plate to produce a polarizing plate (optical laminate) having a structure in which a protective film (COP film), an adhesive layer, a polarizing layer, an adhesive layer, a reddening-resistant layer, a protective film (TAC film), and an adhesive layer were laminated in order.

[0170] Example 2. A polarizing plate was manufactured in the same manner as in Example 1, except that the reddening-resistant layer was changed. The reddening-resistant layer was formed by coating the coating solution of Preparation Example 4 on the same TAC film as in Example 1 using a Mayer bar, drying at 60° C. for 1 minute, and then irradiating the film with ultraviolet light (252 mJ / cm 2 ). 2 ) to a final thickness of 600 nm. The surface area ratio of the formed reddening-resistant layer measured with respect to the surface opposite to the surface in contact with the TAC film was about 0.0359. A polarizing plate was manufactured in the same manner as in Example 1, except that the reddening-resistant layer formed in the above manner was used.

[0171] Example 3. A polarizing plate was manufactured in the same manner as in Example 1, except that the reddening-resistant layer was changed. The reddening-resistant layer was formed in the same manner as in Example 1 using the coating material of Preparation Example 5, but the final thickness was formed to be about 950 nm. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.109. A polarizing plate was manufactured in the same manner as in Example 1, except that the reddening-resistant layer formed as above was used.

[0172] Comparative Example 1 A polarizing plate was prepared in the same manner as in Example 1, except that no reddening-resistant layer was applied.

[0173] Example 4. A polarizing plate was manufactured in the same manner as in Example 1, except that the polarizing layer was the polarizing layer (B) of Preparation Example 2 and the thickness of the reddening-resistant layer was changed to about 300 nm. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.0715.

[0174] Example 5. A polarizing plate was manufactured in the same manner as in Example 1, except that the polarizing layer was the polarizing layer (B) of Preparation Example 2 and the thickness of the reddening-resistant layer was changed to about 400 nm. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.1643.

[0175] Comparative Example 2 A polarizing plate was prepared in the same manner as in Example 4, except that no reddening-resistant layer was applied.

[0176] Example 6. A polarizing plate was manufactured in the same manner as in Example 1, except that the polarizing layer (B) of Preparation Example 2 was used as the polarizing layer, and a reddening-resistant layer having a thickness of about 500 nm was formed by applying the coating material of the reddening-resistant layer of Preparation Example 5. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.2207.

[0177] Example 7. A polarizing plate was manufactured in the same manner as in Example 6, except that the coating material for the reddening-resistant layer of Preparation Example 4 was used. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.0387.

[0178] Example 8. A polarizing plate was manufactured in the same manner as in Example 6, except that the coating material for the reddening-resistant layer of Preparation Example 3 was used. The surface area ratio of the formed reddening-resistant layer measured on the surface in contact with the TAC film and the surface opposite to the TAC film was about 0.0513.

[0179] Example 9 A polarizing plate was manufactured in the same manner as in Example 6, except that the reddening-resistant layer was formed to a thickness of about 3000 nm using the reddening-resistant layer material of Preparation Example 6. The surface area ratio of the formed reddening-resistant layer measured on the surface opposite to the surface in contact with the TAC film was about 0.0611.

[0180] Comparative Example 3. A resin layer was formed on a TAC (Triacetyl cellulose) film (PG601F, Hyosung Co., Ltd.) having a thickness of approximately 60 μm. The resin layer (A) material of Production Example 7 was coated with a Mayer bar, dried at 60° C. for about 1 minute, and then irradiated with ultraviolet light (252 mJ / cm 2) to form a resin layer with a final thickness of about 450 nm. The surface area ratio (Surface Area Ratio) measured for the surface of the formed resin layer opposite to the surface in contact with the TAC film was about 0.01. A general optical water-based adhesive layer (thickness: 100 nm) was applied to the polarizing layer (A) obtained in Preparation Example 1, and a COP (Cycloolefin Polymer) film (manufacturer: Zeon) with a thickness of about 30 μm was attached as a protective film. The formed resin layer was attached to the polarizing layer (A) of the laminate of the COP film and the polarizing layer (A) produced above with the same water-based adhesive (thickness: 100 nm) as above. Next, an acrylic adhesive layer was formed on the lower part of the polarizing plate to produce a polarizing plate (optical laminate) having a structure in which a protective film (COP film), an adhesive layer, a polarizing layer, an adhesive layer, a resin layer, a protective film (TAC film), and an adhesive layer were sequentially laminated.

[0181] The properties of the reddening-resistant layers formed in the above respective Examples are summarized and shown in Table 1 below (in the cases of Comparative Examples 1 and 2, no reddening-resistant layer was formed, and in the case of Comparative Example 3, the properties of the resin layer are shown).

[0182] [Table 1]

[0183] After the heat resistance test was performed on the examples and comparative examples, the single transmittance and color coordinate a * The amount of change in transmittance was evaluated and summarized in Table 2 below. The heat resistance test was performed by laminating the entire upper and lower surfaces of the polarizing plates manufactured in each Example or Comparative Example with soda lime glass (Sewon Tech Co., Ltd.) having a thickness of about 1.1 mm, and then maintaining the temperature at 105°C for 250 hours. In addition, it was observed whether reddening was observed with the naked eye, and if it was observed, it was rated NG, and if it was not observed, it was rated PASS, and the results are summarized in Table 2 below (the unit of transmittance in Table 2 below is %).

[0184] [Table 2]

Claims

1. A display device comprising a cover glass and an optical stack, The optical laminate includes an optical functional layer, a reddening-resistant layer formed on one surface of the optical functional layer, and a pressure-sensitive adhesive layer, the reddening-resistant layer is located between the cover glass and the optical functional layer; the optical laminate is attached to the cover glass by the pressure-sensitive adhesive layer, the reddening-resistant layer is a void-containing layer or a laminate including a void-containing layer, the void-containing layer including hollow particles; the pore size of the hollow particles is in the range of 0.5 to 100 nm; The optical laminate has a CIE L * a * b * Color coordinates a * The absolute value of the change in the display device is within 2: [Formula 1] △a * =a * a -a * i In Equation 1, Δa * is the color coordinate a * is the change in * a is the color coordinate a after maintaining the upper and lower surfaces of the optical laminate in contact with glass substrates at 105° C. for 250 hours. * and a * i is the color coordinate a before being maintained at 105° C. for 250 hours * It is.

2. 2. The display device of claim 1, wherein the absolute value of the change in transmittance according to the following Equation 2 is within 5%: [Formula 2] △Ts=T a -T i In Equation 2, ΔTs is the amount of change in the transmittance, and T a is the transmittance of the optical laminate after the upper and lower surfaces of the optical laminate are brought into contact with glass substrates and maintained at 105° C. for 250 hours, and T i is the transmittance of the optical laminate before being maintained at 105° C. for 250 hours.

3. 3. The display device according to claim 1, wherein the optically functional layer is a polarizing layer or a retardation layer.

4. 4. The display device according to claim 1, wherein the optically functional layer is an iodine-based polarizing layer.

5. The display device according to any one of claims 1 to 4, wherein the reddening-resistant layer satisfies the following formula 4: [Formula 4] H L ≦0.9×H P In Equation 4, H L is the thermal diffusivity of a laminate of a polymer film and the reddening-resistant layer formed on one side of the polymer film, and H P is the thermal diffusivity of the polymer film, and the polymer film is a TAC (triacetyl cellulose) film having a thickness of 60 μm.

6. 6. The display device according to claim 1, wherein the reddening-resistant layer comprises a surface having a surface area ratio of 0.02 or more as measured by an atomic force microscope.

7. 7. The display device according to claim 1, wherein the reddening-resistant layer has a reflectance of 2% or more for light having a wavelength of 800 nm to 1300 nm.

8. The display device according to any one of claims 1 to 7, wherein the diameter of the voids is in the range of 0.5 to 100 nm.

9. The reddening-resistant layer is 0.06 to 0.209 nm in the log value graph of the scattering intensity of small-angle X-ray scattering. -1 9. A display device according to any one of the preceding claims, exhibiting at least one peak within a range of scattering vectors of

10. The display device according to any one of claims 1 to 9, wherein the reddening-resistant layer satisfies the following mathematical formula 6, in which the value of A is 1.5 or less, the value of B is within the range of 0 to 0.01, and the value of C is within the range of 0 to 0.001: [Formula 6] [0010] In Equation 6, n(λ) is the refractive index of the reddening-resistant layer at a wavelength λ, where λ is any wavelength within the range of 300 to 1800 nm.

11. The display device according to any one of claims 1 to 10, wherein the void-containing layer has a void volume fraction of 0.1 or more.

12. The display device of any one of claims 1 to 11, wherein the void-containing layer comprises a binder.

13. 13. The display device of claim 12, wherein the binder comprises a polymerized product of a multifunctional acrylate having in the range of 2 to 10 polymerizable functional groups.

14. The display device according to any one of claims 1 to 13, wherein the hollow particles have D10 particle size, D50 particle size and D90 particle size in the ranges of 25 nm to 50 nm, 50 nm to 95 nm and 100 nm to 200 nm, respectively, in a weight accumulation curve of particle size distribution.

15. The display device of any one of claims 1 to 14, wherein the void-containing layer is free of solid particles.

16. The display device according to any one of claims 1 to 15, wherein the reddening-resistant layer has a thickness of 200 nm or more.

17. A display device according to any preceding claim, wherein the reddening-resistant layer does not form the outermost surface.

18. 18. A display device according to any one of the preceding claims, wherein the optical stack comprises a further layer, and a reddening-resistant layer is present between the further layer and the optically functional layer.

19. 19. The display device of claim 18, wherein the further layer is a protective film, an adhesive layer, a hard coat layer, a retardation layer or a brightness enhancing layer.

20. The display device according to any one of claims 1 to 19, wherein the optical laminate has a surface reflectance of 2% or more for light having a wavelength of 380 nm to 780 nm.

21. The display device according to any one of claims 1 to 20, wherein the distance between the reddening-resistant layer and the optically functional layer is within 90 µm.

Citation Information

Patent Citations

  • Polarizing film with adhesive layer, and image display device

    JP2016157077A

  • Polarizing plate and image display device

    JP2019028196A

  • Dye-containing polarizing plate having cured resin layer

    WO2010095447A1

  • Coating material containing organic / inorganic composite, organic / inorganic composite film and antireflection member

    WO2012115057A1